Diaphragm, secondary battery, and electric device
Patent Information
- Application Number
- CN202380053928.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-20
- Publication Date
- 2025-02-25
AI Technical Summary
In existing secondary batteries, under high energy density design, long cycle, and high temperature conditions, the electrodes are easily damaged, resulting in battery capacity attenuation, and the electrolyte components have poor compatibility, which limits the personalized design and cost of the battery.
A separator including a barrier layer is used. The barrier layer is composed of a polymer layer and a barrier material. The barrier material is a micro-mesoporous material and an ion-conducting inorganic material. By regulating the volume average particle size and layer thickness of the barrier material, the air permeability of the separator is improved. Only lithium ions are allowed to pass through, and solvents, additives and by-products in the electrolyte are inhibited from passing through.
It effectively reduces electrode damage, extends the cycle life of the battery, improves storage performance and cycle performance, reduces battery capacity attenuation, and allows for more flexible electrolyte design, reducing costs.
Smart Images

Figure 00000027_0000 
Figure 00000030_0000 
Figure 00000030_0001
Abstract
Description
Diaphragm, secondary battery and electrical device Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to a diaphragm, a secondary battery, and an electrical device. Background Art
[0002] Secondary batteries are widely used in various consumer electronics and electric vehicles due to their outstanding features such as light weight, pollution-free operation, and lack of memory effect. With the continuous development of the new energy industry, users are placing higher demands on secondary batteries, such as higher energy density, longer cycle life, and greater environmental adaptability. However, high energy density, long cycle life, and high temperatures often lead to severe damage to the electrodes, causing battery capacity degradation.
[0003] Summary of the Invention
[0004] In view of the technical problems existing in the background technology, the present application provides a diaphragm, a secondary battery and an electrical device, aiming to reduce damage to the electrodes and reduce battery capacity attenuation.
[0005] To achieve the above-mentioned object, a first aspect of the present application provides a membrane, comprising a barrier layer, wherein the barrier layer comprises a polymer layer and a barrier material at least partially embedded in the polymer layer;
[0006] The barrier material includes one or more of a micro-mesoporous material and an ion-conducting inorganic material; the volume average particle size Dv50 of the barrier material is denoted as D, the thickness of the barrier layer is denoted as d1, and the volume average particle size Dv50 of the barrier material and the thickness of the barrier layer satisfy: 0.2≤d1 / D≤1000;
[0007] The air permeability of the barrier layer is ≥300s / 100mL.
[0008] Compared with the prior art, this application has at least the following beneficial effects:
[0009] The diaphragm of the present application includes a barrier layer, which includes a polymer layer and a barrier material. By regulating the volume average particle size Dv50 of the barrier material and the thickness of the barrier layer, the permeability of the barrier layer is ≥300s / 100mL. It is difficult for gas to pass through the barrier layer, indicating that most of the pores in the polymer layer have been filled with the barrier material; compared with gas, the solvents, additives and interfacial reaction by-products in the positive electrode electrolyte and the negative electrode electrolyte have greater difficulty passing through the barrier layer. Only lithium ions can penetrate the barrier layer through the barrier material, which greatly inhibits the solvents, additives and by-products in the electrolyte from passing through the barrier layer, eliminating the battery capacity decay caused by the interaction between the positive and negative electrodes.
[0010] In any embodiment of the present application, the air permeability of the barrier layer is ≥500s / 100mL; optionally, the air permeability of the barrier layer is ≥800s / 100mL.
[0011] In any embodiment of the present application, the volume average particle size Dv50 of the barrier material and the thickness of the barrier layer satisfy: 1≤d1 / D≤500; optionally 1≤d1 / D≤300.
[0012] In any embodiment of the present application, the volume average particle size Dv50 of the barrier material satisfies: 0.005 μm ≤ D ≤ 10 μm; optionally 0.007 μm ≤ D ≤ 5 μm; further optionally 0.01 μm ≤ D ≤ 1 μm.
[0013] In any embodiment of the present application, the thickness of the barrier layer satisfies: 0.007 μm ≤ d1 ≤ 50 μm; optionally 0.2 μm ≤ d1 ≤ 15 μm.
[0014] In any embodiment of the present application, the micro-mesoporous material comprises one or more of a covalent organic framework material and a metal organic framework material;
[0015] Optionally, the linking groups between the monomers polymerized to form the covalent organic framework material include One or more of boryloxy, -C=N-, triazine group, -C=NN=C-, -C=C-, -CO-NH-, -C=N-NH-CO- and imidazole group.
[0016] In any embodiment of the present application, the ion-conducting inorganic material includes LLZO, LLTO, LATP, LAGP, LSPS, and one or more of the coatings, dopants and / or dopants with coating layers of the above substances.
[0017] In any embodiment of the present application, the pore size of the internal pores of the micro-mesoporous material is denoted as d2, and the pore size of the internal pores of the micro-mesoporous material satisfies: 0.04nm≤d2≤5nm; optionally 0.3nm≤d2≤2nm.
[0018] In any embodiment of the present application, the electrical conductivity of the ion-conducting inorganic material is ≥ 0.0001 mS·cm at 25°C. -1 ;
[0019] Optionally, the electrical conductivity of the ion-conducting inorganic material is ≥0.001 mS·cm at 25°C. -1 ;
[0020] Further optionally, the electrical conductivity of the ion-conducting inorganic material is ≥0.01 mS·cm at 25°C -1 .
[0021] In any embodiment of the present application, the area proportion of the barrier material in the barrier layer is 30%-99%; optionally 50%-99%; further optionally 70%-99%.
[0022] In any embodiment of the present application, the polymer layer has at least one of the following features (1) to (3):
[0023] (1) The polymer layer comprises a polymer having a swelling degree ≤ 10%;
[0024] Optionally, the polymer includes one or more of polyethylene, polypropylene, polyimide and polyvinylidene fluoride;
[0025] (2) The mass proportion of the polymer layer in the barrier layer is ≤50%;
[0026] Optionally, the mass of the polymer layer in the barrier layer is 2%-30%; further optionally, 5%-15%;
[0027] (3) The polymer layer comprises a polymer having a weight average molecular weight of 1W-200W;
[0028] Optionally, the polymer layer comprises a polymer having a weight average molecular weight of 2W-150W;
[0029] Further optionally, the polymer layer includes a polymer with a weight average molecular weight of 10W-100W.
[0030] In any embodiment of the present application, the diaphragm further includes a support layer, and the barrier layer is located on at least one side of the support layer.
[0031] In any embodiment of the present application, the support layer has at least one of the following features (1) to (3):
[0032] (1) The support layer has pores, and the average pore diameter of the pores of the support layer is 20 nm-1000 nm; optionally 100 nm-500 nm;
[0033] (2) The raw material of the support layer includes one or more of polyethylene, polypropylene, polyimide and polyvinylidene fluoride.
[0034] In any embodiment of the present application, the thickness of the separator is 2 μm-12 μm; optionally 3 μm-10 μm; further optionally 5 μm-7 μm.
[0035] In any embodiment of the present application, the diaphragm has at least one of the following characteristics:
[0036] (1) The air permeability of the diaphragm is ≥300s / 100mL; alternatively, the air permeability of the diaphragm is ≥500s / 100mL; further alternatively, the air permeability of the diaphragm is ≥800s / 100mL;
[0037] (2) The tensile strength of the diaphragm is ≥1000 MPa; optionally, the tensile strength of the diaphragm is ≥1200 MPa; further optionally, the tensile strength of the diaphragm is ≥1500 MPa.
[0038] The second aspect of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a positive electrode electrolyte, a negative electrode electrolyte, and the separator as described in the first aspect of the present application;
[0039] The isolation membrane is located between the positive electrode sheet and the negative electrode sheet, the positive electrode electrolyte is located between the positive electrode sheet and the isolation membrane, and the negative electrode electrolyte is located between the negative electrode sheet and the isolation membrane; one or more of the solvents, lithium salts and additives contained in the positive electrode electrolyte and the negative electrode electrolyte are different.
[0040] In any embodiment of the present application, the solvent of the positive electrode electrolyte is different from the solvent of the negative electrode electrolyte;
[0041] Optionally, the solvent of the positive electrode electrolyte includes one or more of carbonate solvents, fluorocarbonate solvents, fluorocarboxylate solvents, sulfone solvents, fluorosulfone solvents, phosphate solvents, borate solvents and nitrile solvents;
[0042] Optionally, the solvent of the negative electrode electrolyte includes one or more of carbonate solvents, carboxylate solvents, ether solvents, fluorinated carboxylate solvents and fluorinated carbonate solvents.
[0043] In any embodiment of the present application, the fluorocarbonate solvent includes one or more of methyl trifluoroethyl carbonate, bis(trifluoromethyl) carbonate, bis(trifluoroethyl) carbonate, 4-trifluoromethyl ethylene carbonate, bisfluoroethylene carbonate, trifluoromethyl trifluoroethyl carbonate, trifluoropropyl carbonate and 2,2-difluoroethyl methyl carbonate;
[0044] The fluorocarboxylate solvent includes one or more of trifluoroethyl 3,3,3-trifluoroacetate, 2,2-difluoroethyl acetate, ethyl difluoroacetate and 2,2,2-trifluoroethyl acetate;
[0045] The sulfone solvent includes one or more of sulfolane, dimethyl sulfone, diethyl sulfone, methyl ethyl sulfone, methyl isopropyl sulfone, dimethyl sulfoxide, diethyl sulfoxide and methyl ethyl sulfoxide;
[0046] The fluorinated sulfone solvent includes one or more of methyl trifluoromethyl sulfone, ethyl trifluoromethyl sulfone, propyl trifluoromethyl sulfone, methyl trifluoroethyl sulfone, methyl trifluoropropyl sulfone, 1,1,2,2-tetrafluoropropyl methyl sulfone, trifluoromethyl isopropyl sulfone and methyl hexafluoroisopropyl sulfone;
[0047] The phosphate ester solvent includes one or more of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, isopropyl phosphate, tris(hexafluoroisopropyl) phosphate and tris(2,2,2-trifluoroethyl) phosphate;
[0048] The borate ester solvent includes one or more of trimethyl borate, triethyl borate, tris(hexafluoroisopropyl) borate and tris(2,2,2-trifluoroethyl) borate;
[0049] The nitrile solvent includes one or more of acetonitrile, succinonitrile, succinonitrile, glutaronitrile, adiponitrile, 1,4-dicyano-2-butene, 1,3,6-hexanetrinitrile, ethylene glycol dipropionitrile ether and 1,2,3-tricyanoethoxy;
[0050] The carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and ethylene carbonate;
[0051] The carboxylate solvent includes one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate and propyl propionate;
[0052] The ether solvent includes one or more of 1,2-dimethoxyethane, tetraethanol dimethyl ether, γ-butyrolactone and tetrahydrofuran.
[0053] In any embodiment of the present application, the lithium salt of the positive electrode electrolyte is different from the lithium salt of the negative electrode electrolyte;
[0054] Optionally, the lithium salt of the positive electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(oxalatoborate);
[0055] Optionally, the lithium salt of the negative electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(oxalatoborate).
[0056] A third aspect of the present application provides an electrical device comprising the secondary battery of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] To more clearly illustrate the technical solution of this application, the following is a brief introduction to the drawings used in this application. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.
[0058] FIG1 is a schematic diagram of the COF-1 structure provided in one embodiment of the present application.
[0059] FIG2 is a schematic diagram of the COF-2 structure provided in one embodiment of the present application.
[0060] FIG3 is a schematic diagram of the COF-3 structure provided in one embodiment of the present application.
[0061] FIG4 is a schematic diagram of the COF-4 structure provided in one embodiment of the present application.
[0062] FIG5 is a schematic diagram of the COF-5 structure provided in one embodiment of the present application.
[0063] FIG6 is a schematic diagram of the COF-6 structure provided in one embodiment of the present application.
[0064] FIG7 is a schematic diagram of the structure of COF-7 provided in one embodiment of the present application.
[0065] FIG. 8 is a schematic diagram of a secondary battery according to an embodiment of the present application.
[0066] FIG. 9 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 8 .
[0067] FIG. 10 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0068] Description of reference numerals:
[0069] 1 Secondary battery; 11 Housing; 12 Electrode assembly; 13 Cover plate; 2 Electrical device. DETAILED DESCRIPTION
[0070] The present application will be further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.
[0071] For the sake of clarity, only some numerical ranges are specifically disclosed herein. However, any lower limit may be combined with any upper limit to form an unspecified range; and any lower limit may be combined with other lower limits to form an unspecified range, and similarly, any upper limit may be combined with any other upper limit to form an unspecified range. In addition, each individually disclosed point or single value may itself serve as a lower limit or upper limit and be combined with any other point or single value, or with other lower limits or upper limits, to form an unspecified range.
[0072] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0073] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0074] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0075] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0076] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0077] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” include the number itself, and “several” in “one or several” means two or more.
[0078] In the description herein, unless otherwise stated, the term "or" is inclusive. That is, the phrase "A or (or) B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist). Unless otherwise stated, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise stated, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0079] Currently, secondary batteries often suffer severe damage to their electrodes and battery capacity decay under conditions such as high energy density, long cycles, and high temperatures. The technical staff of this application analyzed and found that under these conditions, the reactions between the positive electrode, negative electrode, and electrolyte of the battery continue to intensify, producing complex and diverse byproducts. These byproducts propagate through the electrolyte, diffuse between the positive and negative electrodes, and further react on the other side, causing damage to the electrodes and battery capacity decay.
[0080] In addition, some electrolyte components often have different compatibilities with the positive and negative electrodes, and may have a positive effect on one side and a side effect on the other side. In order to balance the two, the electrolyte design has gradually become more complex, which limits the personalized design of the battery and also increases the cost of the battery. In order to take into account both the positive and negative electrodes, the solvents and lithium salts that can be selected for the electrolyte are very limited, and the advantages of each electrolyte component cannot be brought into play.
[0081] The diaphragm provided in the present application includes a barrier layer, which includes a polymer layer and a barrier material at least partially embedded in the polymer layer; wherein the barrier material includes one or more of a micro-mesoporous material and an ion-conducting inorganic material; the volume average particle size Dv50 of the barrier material is denoted as D, and the thickness of the barrier layer is denoted as d1, and the volume average particle size Dv50 of the barrier material and the thickness of the barrier layer satisfy: 0.2≤d1 / D≤1000; the air permeability of the barrier layer is ≥300s / 100mL.
[0082] It should be noted that the barrier material mentioned in this application only allows lithium ions to pass through, while the solvent, additives and interfacial reaction by-products in the electrolyte cannot pass through. The barrier material can be completely embedded in the polymer layer, in which case the thickness of the barrier layer is the same as the thickness of the polymer layer; it can also be partially embedded in the polymer layer and partially exposed outside the polymer layer, in which case the thickness of the barrier layer is the sum of the thickness of the polymer layer and the thickness of the barrier material exposed outside the polymer layer. The polymer layer has a function similar to that of a substrate and can provide space to accommodate the barrier material. The barrier layer can include one barrier material, or it can include two or more barrier materials at the same time; when the barrier layer includes two or more barrier materials, the barrier materials can all be micro-mesoporous materials, or all be ion-conducting inorganic materials, or they can include both micro-mesoporous materials and ion-conducting inorganic materials. Micro-mesoporous materials refer to materials with microporous structures and / or mesoporous structures; micropores refer to pores with a pore diameter less than 2nm, and mesopores refer to pores with a pore diameter of 2nm-50nm. Ion-conducting inorganic materials refer to materials that can conduct metal ions.
[0083] The diaphragm of the present application includes a barrier layer, which includes a polymer layer and a barrier material. By regulating the volume average particle size Dv50 of the barrier material and the thickness of the barrier layer, the permeability of the barrier layer is ≥300s / 100mL. It is difficult for gas to pass through the barrier layer, indicating that most of the pores in the polymer layer have been filled with the barrier material; compared with gas, the solvents, additives and interfacial reaction by-products in the positive electrode electrolyte and the negative electrode electrolyte have greater difficulty passing through the barrier layer. Only lithium ions can penetrate the barrier layer through the barrier material, which greatly inhibits the solvents, additives and by-products in the electrolyte from passing through the barrier layer, eliminating the battery capacity decay caused by the interaction between the positive and negative electrodes.
[0084] The volume average particle size Dv50 of the barrier material and the thickness of the barrier layer mentioned above satisfy the following conditions: 0.2 ≤ d1 / D ≤ 1000. For example, the range may be 0.2 ≤ d1 / D ≤ 900, 0.2 ≤ d1 / D ≤ 800, 0.2 ≤ d1 / D ≤ 700, 0.2 ≤ d1 / D ≤ 600, 0.2 ≤ d1 / D ≤ 500, 0.2 ≤ d1 / D ≤ 400, 0.2 ≤ d1 / D ≤ 300, 0.2 ≤ d1 / D ≤ 200, 0.2 ≤ d1 / D ≤ 100, or 0.2 ≤ d1 / D ≤ 50. If d1 / D is less than the above range, the barrier layer is susceptible to rupture. If d1 / D is greater than the above range, the barrier material particles may be stacked too closely together, resulting in excessive contact areas between the barrier material particles, which may slow the transmission of lithium ions through the barrier material and worsen the battery impedance. As an example, d1 / D can be 0.2, 1, 50, 100, 150, 200, 250, 300, 350, 400, 450, 500, 600, 700, 800, 900 or 1000, etc.
[0085] The Dv50 of the barrier material mentioned above refers to the particle size corresponding to 50% of the barrier material in the volume distribution. For example, this can be measured using the following method: using laser particle size analysis, a barrier layer sample is placed in deionized water and ultrasonicated for 5 minutes to ensure complete dispersion. The dispersion is then placed in a sample tank and tested to obtain the volume-average particle size Dv50 of the barrier material. Optionally, the barrier layer mass can range from 0.05g to 2g, and the volume of deionized water can range from 10mL to 20mL.
[0086] As an example, the thickness of the barrier layer mentioned above can be measured by the following method: first calibrate the micrometer, then place the barrier layer sample between the two anvils, gently rotate the sleeve until a click is heard, and read and record the thickness of the barrier layer.
[0087] The air permeability of the barrier layer mentioned above is ≥300s / 100mL; optionally, the air permeability of the barrier layer is 300s / 100mL-5000s / 100mL; for example, it can be 300s / 100mL-4500s / 100mL, 300s / 100mL-4000s / 100mL, 300s / 100mL-3500s / 100mL, 300s / 100mL-3000s / 100mL, 300s / 100mL-25 100mL, 300s / 100mL-2000s / 100mL, 300s / 100mL-1900s / 100mL, 300s / 100mL-1800s / 100mL, 300s / 100mL-1700s / 100mL, 300s / 100mL-1600s / 100mL, 300s / 100mL-1500s / 100mL, 300s / 100mL-1400s / 100mL, 300s / 100mL-1300s / 100mL, 300s / 100mL-1200s / 100mL, 300s / 100mL-1100s / 100mL or 300s / 100mL-1000s / 100mL, etc. The greater the air permeability of the barrier layer, the better the barrier effect. For example, the air permeability of the barrier layer can be 300s / 100mL, 400s / 100mL, 500s / 100mL, 600s / 100mL, 700s / 100mL, 800s / 100mL, 900s / 100mL, 1000s / 100mL, 1100s / 100mL, 1200s / 100mL, 1300s / 100mL, 1400s / 100mL, 1500s / 100mL, 1600s / 100mL, 1700s / 100mL, 1800s / 100mL, 1900s / 100mL, 2000s / 100mL, 2100s / 100mL, 2200s / 100mL, 2300s / 100mL, 2400s / 100mL, 2500s / 100mL, 2600s / 100mL, 2700s / 100mL, 2800s / 100mL, 2900s / 100mL, 3000s / 100mL, 3100s / 100mL, 3200s / 100mL, 3300s / 100mL, 3400s / 100mL, 3500s / 100mL, 3600s / 100mL, 3700s / 100mL, 3800s / 100mL, 3900s / 100mL, 4000s / 100mL, 4100s / 100mL, 4200s / 100mL, 4300s 0mL, 1800s / 100mL, 1900s / 100mL, 2000s / 100mL, 2300s / 100mL, 2500s / 100mL, 2800s / 100mL, 3000s / 100mL, 3300s / 100mL, 3500s / 100mL, 3700s / 100mL, 4000s / 100mL, 4300s / 100mL, 4500s / 100mL, 4800s / 100mL or 5000s / 100mL, etc.
[0088] As an example, the air permeability of the aforementioned membrane can be tested using the following method: Flatten the barrier layer, select a flat, oil-free location, place it on the outlet of an air compressor, and tighten it. Once the barrier layer is secured, use the weight of the cylinder floating on the liquid to compress the air inside. As the air passes through the sample, the cylinder will fall steadily. Measure the time required for a certain volume of air to pass through the sample, and use this time to calculate the air permeability. The air column volume is 100cc, and the test area is 6.45cm. 2 ; Sample area > 6cm×6cm.
[0089] The inventors of the present application have found through in-depth research that when the separator of the present application satisfies the above-mentioned design conditions and optionally satisfies one or more of the following conditions, the storage performance and cycle performance of the secondary battery can be further improved.
[0090] In some embodiments, the air permeability of the barrier layer is ≥500 s / 100 mL; alternatively, the air permeability of the barrier layer is ≥800 s / 100 mL.
[0091] In some embodiments, the air permeability of the barrier layer is 500 s / 100 mL to 5000 s / 100 mL; alternatively, the air permeability of the barrier layer is 800 s / 100 mL to 5000 s / 100 mL.
[0092] In some embodiments, the volume average particle size Dv50 of the barrier material and the thickness of the barrier layer satisfy: 1≤d1 / D≤500; optionally 1≤d1 / D≤300.
[0093] In some embodiments, the volume average particle size Dv50 of the barrier material satisfies: 0.005 μm ≤ D ≤ 10 μm; for example, it can be 0.005 μm ≤ D ≤ 9 μm, 0.005 μm ≤ D ≤ 8 μm, 0.005 μm ≤ D ≤ 7 μm, 0.005 μm ≤ D ≤ 6 μm, 0.005 μm ≤ D ≤ 5 μm, 0.005 μm ≤ D ≤ 4 μm, 0.005 μm ≤ D ≤ 3 μm, 0.005 μm ≤ D ≤ 2 μm, 0.005 μm ≤ D ≤ 1 μm, 0.005 μm ≤ D ≤ 0.5 μm, 0.005 μm ≤ D ≤ 0.1 μm, 0.005 μm ≤ D ≤ 0.01 μm, etc. When the volume average particle size Dv50 of the barrier material is below the above range, the barrier material particles may be stacked too tightly, resulting in excessive contact surface area between the barrier material particles, which may slow the transmission rate of lithium ions through the barrier material. When the volume average particle size Dv50 of the barrier material is within the above range, the possibility of lithium ions penetrating the diaphragm through the barrier material is high, and the contact surface area between the barrier material particles can be reduced, reducing the impact on the lithium ion transmission rate. As an example, the volume average particle size Dv50 of the barrier material can be 0.005μm, 0.01μm, 0.05μm, 0.1μm, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, or 10μm. Optionally, the volume average particle size Dv50 of the barrier material satisfies the following: 0.007μm≤D≤5μm. Further optionally, the volume average particle size Dv50 of the barrier material satisfies: 0.01 μm≤D≤1 μm.
[0094] In some embodiments, the thickness of the barrier layer satisfies the following conditions: 0.007 μm ≤ d1 ≤ 50 μm; for example, the thickness may be 0.007 μm ≤ L ≤ 45 μm, 0.01 μm ≤ L ≤ 40 μm, 0.05 μm ≤ L ≤ 35 μm, 0.1 μm ≤ L ≤ 30 μm, 0.1 μm ≤ L ≤ 25 μm, 0.1 μm ≤ L ≤ 20 μm, 0.1 μm ≤ L ≤ 15 μm, 0.1 μm ≤ L ≤ 10 μm, 0.1 μm ≤ L ≤ 5 μm, or 0.1 μm ≤ L ≤ 1 μm. When the thickness of the barrier layer exceeds the above range, the ion transmission path is increased, which may deteriorate the battery impedance and the battery volume energy density. When the thickness of the barrier layer is below the above range, the difficulty of processing and preparation is increased. When the thickness of the barrier layer is within the above range, the barrier layer has both excellent ion conductivity and good barrier effect, while being less difficult to process. For example, the thickness of the barrier layer may be 0.007 μm, 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 15 μm, 20 μm, 30 μm, 40 μm or 50 μm, etc. Optionally, the thickness of the barrier layer satisfies: 0.2 μm≤d1≤15 μm.
[0095] In some embodiments, the micro-mesoporous material includes one or more of a covalent organic framework material and a metal organic framework material.
[0096] It should be noted that covalent organic frameworks (COFs) are a class of crystalline organic porous materials that use reversible chemical reactions to connect functional units via covalent bonds into highly ordered two-dimensional layered structures or specific three-dimensional topologies. COFs can be homopolymers or copolymers of multiple monomers.
[0097] It can be understood that the type of monomers that form the COF material and the number of functional groups that the monomers have that can participate in polymer reactions determine the configuration of the COF material and also determine the pore size of the internal pores of the COF material; the larger the pore size of the internal pores of the COF material, the more conducive it is to lithium ion transmission, and the smaller the pore size of the internal pores of the COF material, the better the effect of inhibiting the passage of other substances in the electrolyte except lithium ions.
[0098] It should be noted that other substances in the electrolyte include solvents, additives, and complex and diverse by-products produced when the positive electrode, negative electrode, electrolyte, etc. of the secondary battery react.
[0099] Optionally, the linking groups between monomers polymerized to form a covalent organic framework material include One or more of boryloxy, -C=N-, triazine group, -C=NN=C-, -C=C-, -CO-NH-, -C=N-NH-CO- and imidazole group.
[0100] The linking group mentioned above refers to the linking group between two adjacent monomer units in the covalent organic framework material.
[0101] It should be noted that the structural formula of the above-mentioned cyclic boryl group is The structural formula of the triazine group mentioned above is The structural formula of the above-mentioned imidazole group is The structural formula of the -CO-NH- group mentioned above is The structural formula of the -C=N-NH-CO- group mentioned above is
[0102] As an example, the monomers and the connecting groups between the monomers that are polymerized to form the COF material mentioned above can be determined by the following method: take the barrier layer and soak it in NMP or water for 24 hours; filter the dissolved material powder and re-immerse it in new NMP solvent or water for 2 hours, then ultrasonicate it for 2 hours to fully disperse the particles, repeat the cleaning and ultrasonication process for more than 3 times, and finally obtain the COF material, which is then dried in a vacuum drying oven at 80°C for 24 hours. The X-ray diffraction spectrum is measured by an X-ray powder diffractometer, and the Fourier infrared spectrum and nuclear magnetic resonance spectrum are measured by an infrared spectrometer and a nuclear magnetic resonance spectrometer. The structure of the COF material contained in the isolation film is determined by combining the X-ray diffraction spectrum, Fourier infrared spectrum and nuclear magnetic resonance spectrum of the isolation film, and then the type of monomers that form the COF material and the connecting groups between the monomers are determined. Among them, the X-ray powder diffractometer can be a Science Ultima IV X-ray powder diffractometer, and the infrared spectrometer can be a Bruker ALPHA with a wavelength range of 400 cm -1 ~4000cm -1 The infrared spectrometer and the nuclear magnetic resonance spectrometer can be a Bruker AV III 400 nuclear magnetic resonance spectrometer.
[0103] Metal-organic frameworks (MOFs) are a class of crystalline porous materials with a periodic network structure formed by self-assembly of inorganic metal centers and bridging organic ligands. The inorganic metal centers can be one or more of metal ions and metal clusters.
[0104] In some embodiments, the ion-conducting inorganic material includes LLZO, LLTO, LATP, LAGP, LSPS, and one or more of coatings, dopants, and / or dopants with coating layers thereof.
[0105] It should be noted that LLZO is a lithium lanthanum zirconium oxide solid electrolyte, LLTO is a lithium lanthanum titanium oxide solid electrolyte, LATP is a lithium aluminum titanium phosphate solid electrolyte, and LAGP is a Li 1.5 Al 0.5 Ge 1.5 (PO4)3, LSPS is a sulfide solid electrolyte. LLZO, LLTO, LATP, and LAGP have synthetic conductivity and good stability. LSPS has significantly higher conductivity and good ion conductivity. These ion-conducting inorganic materials can conduct lithium ions, allowing them to penetrate the barrier layer.
[0106] The coating refers to the substance obtained after forming a coating layer on at least part of the outer surface of each of the above-mentioned materials. The dopant refers to the substance formed after adding one or more of transition metal elements and non-transition metal elements to each of the above-mentioned materials. The doped material with a coating layer refers to the substance obtained after forming a coating layer on at least part of the outer surface of the doped material of each of the above-mentioned materials.
[0107] In some embodiments, the pore diameter of the internal pores of the micro-mesoporous material is denoted as d2, and the pore diameter of the internal pores of the micro-mesoporous material satisfies: 0.04 nm ≤ d2 ≤ 5 nm; for example, it can be 0.04 nm ≤ d2 ≤ 4.5 nm, 0.1 nm ≤ d2 ≤ 4 nm, 0.1 nm ≤ d2 ≤ 3 nm, 0.1 nm ≤ d2 ≤ 2 nm, 0.1 nm ≤ d2 ≤ 1 nm or 0.1 nm ≤ d2 ≤ 0.5 nm, etc. When the pore diameter of the internal pores of the micro-mesoporous material satisfies the above range, only the desolvated lithium ions can penetrate the separator through the internal pores of the micro-mesoporous material, preventing other substances in the electrolyte except lithium ions from penetrating the separator, and inhibiting the interaction between the positive electrode and the negative electrode. For example, the pore diameter of the internal pores of the micro-mesoporous material can be 0.04 nm, 0.1 nm, 0.3 nm, 0.4 nm, 0.7 nm, 1 nm, 1.3 nm, 1.5 nm, 1.8 nm, 2 nm, 3 nm, 4 nm or 5 nm, etc. Optionally, the pore diameter of the internal pores of the micro-mesoporous material satisfies: 0.3 nm ≤ d2 ≤ 2 nm; the inhibitory effect on the interaction between the positive and negative electrodes can be further enhanced.
[0108] As an example, the pore diameter of the internal pores of the above-mentioned COF material can be measured by the following method: Place the barrier layer in NMP or water and soak for 24 h; filter the dissolved material powder, and put it back into a new NMP solvent or water and soak for 2 h, then ultrasonic for 2 h to fully disperse the particles, repeat the cleaning and ultrasonic process more than 3 times, finally obtain the COF material, and place it in a vacuum drying oven at 80 °C and dry for 24 h. Use a gas adsorption instrument to measure the adsorption amount of N2 by the COF material under standard atmospheric pressure (101 kPa), and the purity of the gas used for testing is 99.999%; add 100 mg of the COF material to a quartz sample tube, and degas it under vacuum at 120 °C for 6 h on the pretreatment station of a rapid specific surface area analyzer. Conduct a gas adsorption experiment on the COF material using a gas adsorption instrument. According to the obtained nitrogen adsorption curve, use the non-local density functional theory model (NLDFT) to calculate the BET specific surface area of the COF material for the adsorption data in the low-pressure range (0.0255 < P / P0 < 0.2), and calculate the pore volume at P / P0 = 0.99; the pore size distribution (PSD) is obtained by calculating using the non-local density function theory (NLDFT).
[0109] Understandably, the inorganic metal centers and organic ligands that form the MOF material determine the structure of the MOF material, and the structure of the MOF material determines the pore size of the internal pores.
[0110] As an example, the pore size of the internal pores of the above-mentioned MOF material can be measured by the following method: Place the barrier layer in NMP or water and soak for 24 h; Filter the dissolved material powder, and re-immerse it in a new NMP solvent or water for 2 h, and then ultrasonic for 2 h to fully disperse the particles. Repeat the cleaning and ultrasonic process more than 3 times. Finally, obtain the MOF material and place it in a vacuum drying oven at 80 °C for 24 h. Use a gas adsorption instrument to measure the adsorption amount of N2 by the MOF material under standard atmospheric pressure (101 kPa), and the purity of the gas used for the test is 99.999%; Add 100 mg of the MOF material to a quartz sample tube and degas it under vacuum at 120 °C for 6 h on the pretreatment station of a rapid specific surface area analyzer. Conduct a gas adsorption experiment on the MOF material using a gas adsorption instrument. According to the obtained nitrogen adsorption curve, use the non-local density functional theory model (NLDFT) to calculate the BET specific surface area of the MOF material for the adsorption data in the low-pressure range (0.0255 < P / P0 < 0.2), and calculate the pore volume at P / P0 = 0.99; The pore size distribution (PSD) is obtained by calculation using the non-local density functional theory (NLDFT).
[0111] In some embodiments, the conductivity of the ion-conducting inorganic material ≥ 0.0001 mS·cm at 25 °C -1 ; When the conductivity of the ion-conducting inorganic material is lower than the above range, it may increase the battery impedance and deteriorate the battery kinetic performance. Optionally, the conductivity of the ion-conducting inorganic material ≥ 0.001 mS·cm at 25 °C -1 . Further optionally, the conductivity of the ion-conducting inorganic material ≥ 0.01 mS·cm at 25 °C -1 .
[0112] As an example, the conductivity of the above-mentioned ion-conducting inorganic material can be measured by the following method: Make the ion-conducting inorganic material into a solid electrolyte ceramic sample, conduct an AC impedance test on the solid electrolyte ceramic sample through a CHI660E electrochemical workstation, clamp the sample with a conductive silver paste as the electrode (i.e., silver plating on both sides of the electrolyte wafer), and the test frequency range is 10^6 Hz - 0.1 Hz. After obtaining the total impedance value by analyzing the impedance spectrum obtained by the test, calculate the corresponding total ionic conductivity. The ionic conductivity is calculated according to the formula σ = d / (R×P)×1000. Where σ is the ionic conductivity, and the unit is mS·cm -1, d is the thickness of the electrolyte sheet, in cm; R is the impedance value of the electrolyte sheet measured by the electrochemical workstation, in ohms; P is the bottom area of the electrolyte sheet, in cm 2 .
[0113] In some embodiments, the barrier material accounts for 30% to 99% by area in the barrier layer; for example, it may be 35% to 99%, 40% to 99%, 50% to 99%, 60% to 99%, 70% to 99%, 80% to 99%, or 90% to 99%. When the barrier material accounts for less than the above range per unit area in the barrier layer, it may result in too few lithium ion transmission channels, which may increase battery impedance. As an example, the barrier material accounts for 30%, 40%, 50%, 60%, 70%, 80%, 90%, or 99% per unit area in the barrier layer. Alternatively, the barrier material accounts for 50% to 99% per unit area in the barrier layer. Further alternatively, the barrier material accounts for 70% to 99% per unit area in the barrier layer.
[0114] It should be noted that the area ratio refers to the ratio of the area of the barrier material to the total area of the barrier layer.
[0115] As an example, the area ratio of the barrier material in the barrier layer can be tested by the following method: use a scanning electron microscope to take an SEM image of the barrier layer, and calculate the total area of the barrier material and the area of the barrier layer based on the SEM image of the barrier layer; according to the formula: total area of the barrier material / area of the barrier layer, calculate the area ratio of the barrier material in the barrier layer.
[0116] In some embodiments, the polymer layer includes a polymer with a swelling degree of 10% or less. Optionally, the swelling degree of each polymer in the polymer layer is 10% or less. When the swelling degree of the polymer meets the above range, the polymer does not swell in the electrolyte solvent, has good stability, and can inhibit the electrolyte from penetrating the barrier layer.
[0117] Optionally, the polymer includes one or more of polyethylene, polypropylene, polyimide and polyvinylidene fluoride.
[0118] It should be noted that the polymer layer may include only one type of polymer, or may include two or more types of polymers at the same time.
[0119] As an example, the swelling degree of the above-mentioned polymer can be measured by the following method: take a barrier layer sample, measure its thickness with a vernier caliper or a micrometer screw, and calculate its volume as T1; add the barrier layer sample into dimethyl carbonate and soak it for 12 hours; then measure the length, width and height of the barrier layer sample after removal, and calculate its volume as T2; then calculate the swelling degree of the polymer according to the formula C = (T2-T1) / T1×100%.
[0120] In some embodiments, the mass proportion of the polymer layer in the barrier layer is ≤50%. When the mass proportion of the polymer in the barrier layer exceeds the above range, the lithium ion transmission speed may be significantly slowed down, which may worsen the battery impedance.
[0121] Optionally, the polymer layer accounts for 2%-30% by weight of the barrier layer; for example, it may be 2%-25%, 2%-20%, 2%-15%, 2%-10%, or 2%-5%. As an example, the polymer layer may account for 2%, 5%, 10%, 15%, 20%, 25%, or 30% by weight of the barrier layer. Further optionally, the polymer layer accounts for 5%-15% by weight of the barrier layer.
[0122] As an example, the mass proportion of the above-mentioned polymer layer in the barrier layer can be tested by the following method: Use a thermogravimetric-differential scanning calorimeter to analyze the components of the barrier layer: take 15-25 mg of the barrier layer, place it in an alumina crucible, use nitrogen as a protective gas, preheat at 25°C for 30 minutes, and then raise the temperature to 600°C at a rate of 2°C / 10 minutes. Determine the content of each component based on the weight change and heat change.
[0123] In some embodiments, the polymer layer includes a polymer having a weight-average molecular weight of 1W-200W. Optionally, the polymer contained in the polymer layer has a weight-average molecular weight of 1W-200W; for example, it can be 1W-180W, 1W-160W, 1W-140W, 1W-120W, 1W-100W, 1W-80W, 1W-60W, 1W-40W, or 1W-20W. If the weight-average molecular weight of the polymer contained in the polymer layer is lower than the above range, it may not meet the strength requirements of the barrier layer. As an example, the weight average molecular weight of the polymer contained in the polymer layer can be 1W, 10W, 20W, 30W, 40W, 50W, 60W, 70W, 80W, 90W, 100W, 110W, 120W, 130W, 140W, 150W, 160W, 170W, 180W, 190W or 200W. Alternatively, the polymer layer includes a polymer having a weight average molecular weight of 2W-150W. Further optionally, the polymer layer includes a polymer having a weight average molecular weight of 10W-100W.
[0124] As an example, the weight average molecular weight of the above-mentioned polymers can be measured by gel permeation chromatography (GPC).
[0125] In some embodiments, the diaphragm further comprises a support layer, wherein the barrier layer is located on at least one side of the support layer. Providing the support layer can improve the strength of the diaphragm. In some embodiments, the support layer has pores, and the average pore size of the pores of the support layer is 20 nm to 1000 nm; for example, the pores may be 20 nm to 900 nm, 20 nm to 800 nm, 20 nm to 700 nm, 20 nm to 600 nm, 20 nm to 500 nm, 20 nm to 400 nm, 20 nm to 300 nm, 20 nm to 200 nm, or 20 nm to 100 nm. As an example, the average pore size of the pores of the support layer may be 20 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, or 1000 nm. Alternatively, the average pore size of the pores of the support layer is 100 nm to 500 nm.
[0126] As an example, the average pore size of the pores in the support layer mentioned above can be tested by the following method: the pore size of the diaphragm is tested using a pore size testing instrument, the sample to be tested is cut into discs with a diameter of 0.5 cm, soaked in the infiltration liquid for 10 minutes, and transferred to the fixture with tweezers, the pressure range is set to 0-500PSI, and the pore size test is performed.
[0127] In some embodiments, the material of the support layer includes one or more of polyethylene, polypropylene, polyimide, and polyvinylidene fluoride.
[0128] In some embodiments, the thickness of the separator is 2 μm to 12 μm; for example, it can be 2 μm to 11 μm, 2 μm to 10 μm, 2 μm to 9 μm, 2 μm to 8 μm, 2 μm to 7 μm, 2 μm to 6 μm, 2 μm to 5 μm, 2 μm to 4 μm, or 2 μm to 3 μm. When the thickness of the separator formed by the support layer and the barrier layer falls within the above range, the strength of the separator can be further improved. As an example, the thickness of the separator can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, or 12 μm. Alternatively, the thickness of the separator is 3 μm to 10 μm. Further alternatively, the thickness of the separator is 5 μm to 7 μm.
[0129] As an example, the thickness of the above-mentioned diaphragm can be measured by the following method: first calibrate the micrometer, then place the diaphragm between the two anvils, gently rotate the sleeve until a sound is heard, and read the thickness of the diaphragm.
[0130] In some embodiments, the separator has an air permeability of 300 s / 100 mL or greater. When the separator's air permeability meets this range, it promotes close contact between the polymer layer and the barrier material, creating a void-free barrier layer. This reduces the transmission of positive and negative electrolytes, as well as interfacial byproducts, and inhibits interaction between the positive and negative electrodes. Alternatively, the separator has an air permeability of 400 s / 100 mL or greater; further preferably, the separator has an air permeability of 500 s / 100 mL or greater.
[0131] It should be noted that air permeability refers to the time it takes for a certain volume of air to pass through a membrane per unit area under unit pressure.
[0132] As an example, the air permeability of the diaphragm mentioned above can be tested using the following method: flatten the diaphragm, select a flat and oil-free location, place it on the air outlet of the air compressor cylinder, and tighten it; after the diaphragm is fixed in place, use the gravity of the cylinder floating on the liquid to compress the air in the cylinder. As the air passes through the sample, the cylinder will fall steadily. Measure the time required for a certain volume of air to pass through the sample, and calculate the air permeability based on this. The volume of the air column is 100cc; the test area is 6.45cm 2 ; Sample area > 6cm×6cm.
[0133] In some embodiments, the tensile strength of the separator is ≥1000 MPa. When the tensile strength of the separator meets the above range, the strength of the barrier layer can be further improved, allowing the barrier layer to maintain good structural strength during battery cell use. Alternatively, the tensile strength of the separator is ≥1200 MPa; further preferably, the tensile strength of the separator is ≥1500 MPa.
[0134] As an example, the tensile strength of the above-mentioned diaphragm can be tested by the following method: cut the diaphragm into 15cm*2cm and measure its thickness as A; then clamp the diaphragm on the universal tester, input the parameters A and 15cm, and start the measurement; when the diaphragm is broken, the tensile strength will be displayed and the tensile strength can be read.
[0135] The present application also provides a method for preparing a diaphragm, comprising the following steps: preparing a solution containing a polymer; loading the solution on a carrier to prepare a polymer layer; loading a barrier material on the surface of the polymer layer before the polymer layer is formed into a film; embedding the barrier material into the polymer layer by rolling, drying, and removing the carrier to prepare the barrier layer.
[0136] Optionally, the mass percentage concentration of the solution containing the polymer can be 2%-20%, optionally 3%-7%. Optionally, the solvent used in preparing the solution containing the polymer includes N-methylpyrrolidone. Optionally, the carrier includes a glass plate. Optionally, the thickness of the polymer layer is 4μm-6μm. Optionally, the solution is loaded on the carrier by a doctor blade method. Further optionally, the height of the doctor blade used in the doctor blade method is 10μm, and the speed of the coater is 25mm / s-35mm / s. Optionally, the drying temperature is 75℃-85℃, and the drying time is 10h-14h.
[0137] It should be noted that the above-mentioned preparation method can be used to prepare a diaphragm containing only a barrier layer.
[0138] As an example, the preparation method of the diaphragm includes the following steps: dissolving the polymer in a solvent until it is clear to obtain a solution with a mass percentage concentration of 3%-7%; scraping the solution onto a glass plate with a coating thickness of 4μm-6μm to obtain a polymer layer loaded on the glass plate, wherein the height of the scraper used for scraping is 10μm, and the coating machine drives the scraper to move at a speed of 25mm / s-35mm / s; before the polymer layer is formed into a film, the barrier material is evenly sprayed on the surface of the polymer layer, and then the barrier material is embedded in the polymer layer by rolling, and the polymer layer is placed in a vacuum drying oven at 75℃-85℃ for 10h-14h, and the glass plate is removed to obtain a barrier layer.
[0139] The present application also provides a method for preparing a diaphragm, comprising the following steps: preparing a slurry containing a polymer and a barrier material; placing the base membrane in a filtration device; adding the slurry to the filtration device, filtering, and drying to prepare a barrier layer.
[0140] Optionally, the solvent used to prepare the slurry containing the polymer and barrier material includes N-methylpyrrolidone. Optionally, when preparing the slurry, the mixture of the polymer, barrier material, and solvent is dispersed at 800-1200 rpm for 10-14 hours. Optionally, the base film includes a PE film. Optionally, the filtration equipment includes a Buchner funnel. Optionally, the filtration time is 1.5-2.5 hours. Optionally, the drying temperature is 75°C-85°C, and the drying time is 10-14 hours.
[0141] It should be noted that the above-mentioned preparation method can be used to prepare a diaphragm containing only a barrier layer.
[0142] As an example, the preparation method of the diaphragm includes the following steps: dissolving the polymer in a solvent until it is clear, adding a barrier material, and dispersing at 800rpm-1200rpm for 10h-14h to obtain a slurry; placing a PE film on a Buchner funnel, spreading it flat in the Buchner funnel, adding the slurry, and filtering for 1.5h-2.5h; then adding deionized water to the Buchner funnel to wash away the residual slurry; removing the PE film from the Buchner funnel and placing it in a vacuum drying oven at 75℃-85℃ to dry it for 10h-14h to obtain a barrier layer.
[0143] The present application also provides a method for preparing a diaphragm, comprising the following steps: preparing a solution containing a polymer; placing the solution on at least one side of a support layer to prepare a polymer layer; before the polymer layer is formed into a film, loading a barrier material on the surface of the polymer layer; embedding the barrier material into the polymer layer by rolling, and drying to prepare a diaphragm.
[0144] Optionally, the mass percentage concentration of the solution containing the polymer can be 2%-20%, optionally 3%-7%. Optionally, the solvent used in preparing the solution containing the polymer includes N-methylpyrrolidone. Optionally, the carrier includes a glass plate. Optionally, the thickness of the polymer layer is 4μm-6μm. Optionally, the solution is loaded on the carrier by a doctor blade method. Further optionally, the height of the doctor blade used in the doctor blade method is 10μm, and the speed of the coater is 25mm / s-35mm / s. Optionally, the drying temperature is 75℃-85℃, and the drying time is 10h-14h.
[0145] It should be noted that the above-mentioned preparation method can be used to prepare a diaphragm comprising both a barrier layer and a support layer.
[0146] As an example, the preparation method of the diaphragm includes the following steps: dissolving the polymer in a solvent until it is clear to obtain a solution with a mass percentage concentration of 3%-7%; coating the solution on a PE base film with a coating thickness of 4μm-6μm to obtain a polymer layer loaded on the PE base film, wherein the height of the scraper used in the scraping is 10μm, and the coating machine drives the scraper to move at a speed of 25mm / s-35mm / s; before the polymer layer is formed into a film, the barrier material is evenly sprayed on the surface of the polymer layer, and the barrier material is embedded in the polymer layer by rolling; and then dried in a vacuum drying oven at 75℃-85℃ for 10h-14h to obtain a diaphragm.
[0147] The present application also provides a method for preparing a diaphragm, comprising the following steps: preparing a slurry containing a polymer and a barrier material; placing the slurry on a support layer, drying, and preparing a primary treatment barrier layer; placing the primary treatment barrier layer in a filtration device; adding a solution containing a polymer to the filtration device, filtering, and drying to prepare a diaphragm.
[0148] Optionally, the solvent used to prepare the slurry containing the polymer and barrier material includes N-methylpyrrolidone. Optionally, when preparing the slurry, the mixture of the polymer, barrier material, and solvent is dispersed at 1800-2200 rpm for 10-14 hours. Optionally, the base film includes a PE film. Optionally, the filtration equipment includes a Buchner funnel. Optionally, the filtration time is 1.5-2.5 hours. Optionally, the drying temperature is 75°C-85°C, and the drying time is 10-14 hours.
[0149] It should be noted that the above-mentioned preparation method can be used to prepare a diaphragm comprising both a barrier layer and a support layer.
[0150] As an example, the preparation method of the diaphragm includes the following steps: dissolving the polymer in a solvent until it is clear, adding a barrier material, and dispersing at 1800rpm-2200rpm for 10-14h to obtain a slurry; scraping the solution on a PE film with a coating thickness of 1.5μm-2.5μm, wherein the height of the scraper used during scraping is 5μm, and the coater drives the scraper to move at a speed of 25mm / s-35mm / s; then placing it in a vacuum drying oven at 75℃-85℃ for 10h-14h to obtain a once-treated barrier layer loaded on the PE film; spreading the PE film and the once-treated barrier layer flat in a Buchner funnel, adding a polymer solution with a mass percentage concentration of 3%-5%, and filtering for 1.5h-2.5h; then adding deionized water to the Buchner funnel to wash away the residual polymer solution; removing the PE film from the Buchner funnel and placing it in a vacuum drying oven at 75℃-85℃ for 10h-14h to obtain a diaphragm.
[0151] secondary batteries
[0152] The present application also provides a secondary battery comprising a positive electrode sheet, a negative electrode sheet, a positive electrolyte, a negative electrolyte, and the separator described above; the separator is positioned between the positive electrode sheet and the negative electrode sheet, the positive electrolyte is positioned between the positive electrode sheet and the separator, and the negative electrolyte is positioned between the negative electrode sheet and the separator; the positive and negative electrolytes contain different solvents, lithium salts, and additives. As a result, the resulting secondary battery has significantly improved storage and cycle performance.
[0153] It should be noted that, in some possible embodiments, when preparing a secondary battery, the positive electrode sheet and the negative electrode sheet can be stacked close to the isolation membrane, and then the three can be placed in an aluminum-plastic bag with the same length and width as the isolation membrane. Since the isolation membrane and the aluminum-plastic bag are the same length and width, the other three sides except the opening of the aluminum-plastic bag can be heat-sealed together with the isolation membrane. The isolation membrane and the aluminum-plastic bag form a dense positive electrode chamber and a negative electrode chamber, and then the positive electrode electrolyte and the negative electrode electrolyte are respectively injected into the positive electrode chamber and the negative electrode chamber from the opening of the aluminum-plastic bag. Finally, the opening of the aluminum-plastic bag is heat-sealed to obtain a battery cell, and the battery cell is placed in a shell. For example, the shell can be a steel shell to obtain a secondary battery.
[0154] As a possible embodiment, when preparing a secondary battery, the positive electrode sheet, the negative electrode sheet, and the separator can be wound and then placed in an aluminum-plastic bag. The lower end of the aluminum-plastic bag is heat-sealed together with the separator. The separator and the aluminum-plastic bag form a dense positive electrode chamber and a negative electrode chamber. The positive electrode electrolyte and the negative electrode electrolyte are then injected into the positive electrode chamber and the negative electrode chamber respectively through the opening of the aluminum-plastic bag. Finally, the opening of the aluminum-plastic bag is heat-sealed to obtain a battery cell, which is then placed in a casing, for example, a steel casing, to obtain a secondary battery. It should be noted that in conventional electrolytes, the compatibility of solvents, lithium salts, and additives with the positive and negative electrodes is often different. Therefore, it is usually necessary to use a combination of solvents, lithium salts, and additives to simultaneously protect the positive and negative electrodes. In this application, since the diaphragm can inhibit the exchange of positive electrode electrolyte and negative electrode electrolyte, the electrolyte can be designed separately according to the characteristics of the positive electrode and negative electrode themselves without considering the compatibility with the other side; therefore, the advantages of different electrolytes can be further amplified, the performance of the battery cell can be improved, and the limit design of the electrolyte can be pushed.
[0155] The secondary battery, battery module, battery pack, and electric device of the present application are described below with reference to the accompanying drawings as appropriate.
[0156] In some embodiments, the solvent of the positive electrode electrolyte is different from the solvent of the negative electrode electrolyte.
[0157] Understandably, since the separator separates the positive and negative electrolytes, the positive and negative electrolytes can each use a solvent system that matches their respective systems. For example, the positive electrolyte can use an oxidation-resistant solvent system, which can significantly reduce electrolyte oxidation and improve battery cell performance; the negative electrolyte can use a solvent system that is compatible with the negative electrode and has a low viscosity, which can significantly improve the negative electrode interface stability and increase the lithium ion transfer rate at the negative electrode.
[0158] It should be noted that when the types of solvents used in the positive electrode electrolyte and the negative electrode electrolyte are completely different, this falls under the category of having different solvents for the positive electrode electrolyte and the negative electrode electrolyte. For example, if the solvent used in the positive electrode electrolyte is E and the solvent used in the negative electrode electrolyte is F, then the solvents for the positive electrode electrolyte and the negative electrode electrolyte are different.
[0159] When both the positive and negative electrolytes utilize a mixture of multiple solvents, and the solvents used in the positive and negative electrolytes are the same, but the volume or mass ratios of the different solvents differ, this also falls under the category of having different solvents for the positive and negative electrolytes. For example, if the solvent used in the positive electrolyte is a mixture of E and F in a 5:5 volume ratio, and the solvent used in the negative electrolyte is a mixture of E and F in a 3:7 volume ratio, then the solvents for the positive and negative electrolytes are different.
[0160] When the positive and negative electrolytes use some of the same solvents, this also falls under the category of having different solvents for the positive and negative electrolytes. For example, if the positive electrolyte uses solvent E and the negative electrolyte uses a mixture of E and F, then the solvents for the positive and negative electrolytes are different. If the positive electrolyte uses a mixture of E and G, and the negative electrolyte uses a mixture of E and F, then the solvents for the positive and negative electrolytes are also different.
[0161] Optionally, the solvent of the positive electrode electrolyte includes one or more of carbonate solvents, fluorinated carbonate solvents, fluorinated carboxylate solvents, sulfone solvents, fluorinated sulfone solvents, phosphate solvents, borate solvents and nitrile solvents.
[0162] Optionally, the solvent of the negative electrode electrolyte includes one or more of a carbonate solvent, a carboxylate solvent, an ether solvent, a fluorinated carboxylate solvent, and a fluorinated carbonate solvent.
[0163] In some embodiments, the fluorocarbonate solvents include one or more of methyl trifluoroethyl carbonate, bis(trifluoromethyl) carbonate, bis(trifluoroethyl) carbonate, 4-trifluoromethyl ethylene carbonate, bisfluoroethylene carbonate, trifluoromethyl trifluoroethyl carbonate, trifluoropropyl carbonate, and 2,2-difluoroethyl methyl carbonate; the fluorocarboxylate solvents include one or more of 3,3,3-trifluoroethyl trifluoroacetate, 2,2-difluoroethyl acetate, ethyl difluoroacetate, and 2,2,2-difluoroethyl acetate. One or more of trifluoroethyl esters; sulfone solvents include one or more of sulfolane, dimethyl sulfone, diethyl sulfone, methyl ethyl sulfone, methyl isopropyl sulfone, dimethyl sulfoxide, diethyl sulfoxide and methyl ethyl sulfoxide; fluorosulfone solvents include one or more of methyl trifluoromethyl sulfone, ethyl trifluoromethyl sulfone, propyl trifluoromethyl sulfone, methyl trifluoroethyl sulfone, methyl trifluoropropyl sulfone, 1,1,2,2-tetrafluoropropyl methyl sulfone, trifluoromethyl isopropyl sulfone and methyl hexafluoroisopropyl sulfone; phosphate esters The solvent includes one or more of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, isopropyl phosphate, tris(hexafluoroisopropyl) phosphate and tris(2,2,2-trifluoroethyl) phosphate; the borate solvent includes one or more of trimethyl borate, triethyl borate, tris(hexafluoroisopropyl) borate and tris(2,2,2-trifluoroethyl) borate; the nitrile solvent includes acetonitrile, succinonitrile, succinonitrile, glutaronitrile, adiponitrile, 1,4-dicyano-2-butene, 1,3,6 -hexane trinitrile, ethylene glycol dipropionitrile ether and 1,2,3-tricyanoethoxy; carbonate solvents include one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and ethylene carbonate; carboxylic acid ester solvents include one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate and propyl propionate; ether solvents include one or more of 1,2-dimethoxyethane, tetraethanol dimethyl ether, γ-butyrolactone and tetrahydrofuran.
[0164] Optionally, the solvent of the positive electrode electrolyte includes one or more of bis(trifluoromethyl)carbonate, bis(trifluoroethyl)carbonate, bisfluoroethylene carbonate, 2,2-difluoroethyl acetate, ethyl difluoroacetate, diethyl sulfone, methyl ethyl sulfone, methyl trifluoromethyl sulfone, ethyl trifluoromethyl sulfone, triethyl phosphate, tripropyl phosphate, acetonitrile, succinonitrile and succinonitrile.
[0165] Optionally, the solvent of the negative electrode electrolyte includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, 1,2-dimethoxyethane, and tetraethanol dimethyl ether.
[0166] In some embodiments, the lithium salt of the positive electrode electrolyte is different from the lithium salt of the negative electrode electrolyte.
[0167] It should be noted that when the types of lithium salts contained in the positive electrode electrolyte are completely different from those contained in the negative electrode electrolyte, the lithium salts in the positive electrode electrolyte and the negative electrode electrolyte are considered different. For example, if the lithium salt contained in the positive electrode electrolyte is a and the lithium salt used in the negative electrode electrolyte is b, then the lithium salts in the positive electrode electrolyte and the negative electrode electrolyte are different.
[0168] If the lithium salt type in the positive electrolyte is identical to the lithium salt type in the negative electrolyte, but the mass volume concentration or molar concentration of the lithium salt is different, then the lithium salt in the positive electrolyte and the lithium salt in the negative electrolyte are different. For example, if the lithium salt in the positive electrolyte is a with a molar concentration of 1 mol / L, and the lithium salt in the negative electrolyte is a with a molar concentration of 1.5 mol / L, then the lithium salt in the positive electrolyte and the lithium salt in the negative electrolyte are different.
[0169] When both the positive and negative electrolytes utilize multiple lithium salts, and the types of lithium salts used in the positive and negative electrolytes are exactly the same, but the mass ratios or molar ratios of the different lithium salts are different, this also falls within the category of the lithium salts in the positive and negative electrolytes being different. For example, if the lithium salt in the positive electrolyte is a mixture of a and b in a molar ratio of 5:5, and the lithium salt in the negative electrolyte is a mixture of a and b in a molar ratio of 3:7, then the lithium salts in the positive and negative electrolytes are different. Furthermore, when the types of lithium salts and the molar ratios or mass ratios of the different lithium salts in the positive and negative electrolytes are exactly the same, but the total mass volume concentrations or total molar concentrations of the lithium salts are different, this also falls within the category of the lithium salts in the positive and negative electrolytes being different. For example, the lithium salt in the positive electrode electrolyte and the lithium salt in the negative electrode electrolyte are both a mixture of a and b with a molar ratio of 5:5, but the total molar concentration of the lithium salt in the positive electrode electrolyte is 1 mol / L, and the total molar concentration of the lithium salt in the negative electrode electrolyte is 1.5 mol / L, then the lithium salt in the positive electrode electrolyte is different from the lithium salt in the negative electrode electrolyte.
[0170] When the types of lithium salts in the positive and negative electrolytes are partially the same, the lithium salts in the positive and negative electrolytes are considered different. For example, if the lithium salt in the positive electrolyte is a and the lithium salt in the negative electrolyte is a mixture of a and b, then the lithium salt in the positive and negative electrolytes are different. If the lithium salt in the positive electrolyte is a mixture of a and c and the lithium salt in the negative electrolyte is a mixture of a and c, then the lithium salt in the positive and negative electrolytes are also different.
[0171] In some embodiments, the lithium salt of the positive electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, and lithium bis(oxalatoborate).
[0172] In some embodiments, the lithium salt of the positive electrode electrolyte may further include one or more of lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the lithium salt in the positive electrode electrolyte is typically 0.5 mol / L to 4 mol / L.
[0173] In some embodiments, the lithium salt of the negative electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, and lithium bis(oxalatoborate).
[0174] In some embodiments, the lithium salt of the negative electrode electrolyte may further include one or more of lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the lithium salt in the negative electrode electrolyte is typically 0.5 mol / L to 4 mol / L.
[0175] In some embodiments, the cathode electrolyte may optionally include additives. For example, the additives may include cathode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, or additives that improve battery high or low temperature performance.
[0176] In some embodiments, the negative electrode electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, or additives that improve battery high or low temperature performance.
[0177] During the battery's charge and discharge processes, active ions are embedded in and extracted from the positive and negative electrodes. The positive and negative electrolytes conduct ions between the positive and negative electrodes. A separator, located between the positive and negative electrodes, prevents short circuits while allowing ions to pass through.
[0178] Positive electrode
[0179] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one side of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0180] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0181] In some embodiments, the positive electrode active material may include a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. The weight ratio of the positive electrode active material in the positive electrode film layer is 80-100 weight%, based on the total weight of the positive electrode film layer.
[0182] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material substrate includes but is not limited to at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0183] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0-20 weight%, based on the total weight of the positive electrode film layer.
[0184] In some embodiments, the positive electrode film layer may further optionally include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.
[0185] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40-80wt%, and the viscosity at room temperature is adjusted to 5000-25000mPa·s, and the solvent may include but is not limited to N-methylpyrrolidone, and the positive electrode slurry is coated on both sides of the positive electrode current collector, and after drying, the positive electrode sheet is formed by cold rolling; the unit surface density of the positive electrode powder coated on one side is 150-450mg / m 2 The compaction density of the positive electrode is 2.0-4.3g / cm 3 , optional 3.5-4.3g / cm 3 The calculation formula of the compacted density is
[0186] Compaction density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).
[0187] Negative electrode
[0188] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0189] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0190] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver and silver alloys, etc., and the polymer material substrate includes but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and other substrates.
[0191] In some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode film layer is 70-100 weight%, based on the total weight of the negative electrode film layer.
[0192] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The binder may be present in the negative electrode film layer in an amount of 0-30% by weight, based on the total weight of the negative electrode film layer.
[0193] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0-20% by weight, based on the total weight of the negative electrode film layer.
[0194] In some embodiments, the negative electrode film layer may further include other additives, such as thickeners. Thickeners include, but are not limited to, sodium carboxymethyl cellulose (CMC-Na). The weight ratio of the other additives in the negative electrode film layer is 0-15% by weight, based on the total weight of the negative electrode film layer.
[0195] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a negative electrode slurry, wherein the negative electrode slurry has a solid content of 30-70wt% and a viscosity at room temperature adjusted to 2000-10000mPa·s, and the solvent may include but is not limited to deionized water; the obtained negative electrode slurry is coated on both sides of the negative electrode current collector, and after a drying process, cold pressing, such as with a roller, is performed to obtain the negative electrode sheet. The unit surface density of the negative electrode powder coated on one side is 75-220mg / m 2 , the compaction density of the negative electrode is 1.2-2.0g / m 3 .
[0196] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0197] When preparing the electrode assembly by the lamination process, the positive electrode sheet and the negative electrode sheet are placed close to the separator, and then the three are placed in an aluminum-plastic bag with the same length and width as the separator. The other three sides except the opening of the aluminum-plastic bag are heat-sealed together with the separator. The separator and the aluminum-plastic bag form dense positive and negative electrode chambers, and then the positive electrode electrolyte and the negative electrode electrolyte are injected into the positive electrode chamber and the negative electrode chamber respectively from the opening of the aluminum-plastic bag. Finally, the opening of the aluminum-plastic bag is heat-sealed to obtain the battery cell.
[0198] When preparing the electrode assembly by the winding process, the positive electrode sheet, the negative electrode sheet and the separator can be wound and then placed in an aluminum-plastic bag. The lower end of the aluminum-plastic bag is heat-sealed together with the separator. The separator and the aluminum-plastic bag form a dense positive electrode chamber and a negative electrode chamber. The positive electrode electrolyte and the negative electrode electrolyte are then injected into the positive electrode chamber and the negative electrode chamber respectively from the opening of the aluminum-plastic bag. Finally, the opening of the aluminum-plastic bag is heat-sealed to obtain a battery cell.
[0199] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the battery cell.
[0200] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0201] In some embodiments, the secondary battery is a lithium-ion battery.
[0202] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG8 shows a secondary battery 1 with a square structure as an example.
[0203] In some embodiments, referring to FIG9 , the outer packaging may include a housing 11 and a cover 13 . The housing 11 may include a bottom plate and side plates connected to the bottom plate, which together form a receiving cavity. The housing 11 may have an opening communicating with the receiving cavity, and the cover 13 may be positioned over the opening to seal the receiving cavity.
[0204] The positive electrode sheet, negative electrode sheet, and separator can be wound or laminated to form an electrode assembly 12. The electrode assembly 12 is enclosed in the housing. A positive electrolyte is inserted between the positive electrode sheet and the separator, while a negative electrolyte is inserted between the negative electrode sheet and the separator. The secondary battery 1 can contain one or more electrode assemblies 12, which can be adjusted based on demand.
[0205] In some embodiments, secondary batteries can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0206] In a battery module, multiple secondary batteries can be arranged in sequence along the length of the battery module. Of course, they can also be arranged in any other manner. Furthermore, the multiple secondary batteries can be fixed by fasteners.
[0207] Optionally, the battery module may further include a housing having an accommodation space, and the plurality of secondary batteries are accommodated in the accommodation space.
[0208] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0209] A battery pack may include a battery box and multiple battery modules disposed within the box. The battery box comprises an upper case and a lower case. The upper case can be placed over the lower case to form an enclosed space for accommodating the battery modules. The multiple battery modules can be arranged in any manner within the battery box.
[0210] Electrical devices
[0211] The present application also provides an electrical device comprising at least one of the aforementioned secondary battery, battery module, or battery pack. The secondary battery, battery module, or battery pack can be used as a power source for the device or as an energy storage unit for the device. The device may be, but is not limited to, a mobile device, an electric vehicle, an electric train, a ship, a satellite, an energy storage system, or the like; wherein the mobile device may include, but is not limited to, at least one of a mobile phone and a laptop computer; and the electric vehicle may include, but is not limited to, at least one of a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, or the like.
[0212] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0213] Figure 10 shows an example of an electric device 2. The electric device 2 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module can be used.
[0214] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0215] The beneficial effects of the present application are further illustrated below with reference to the examples.
[0216] Example
[0217] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application. The materials used in the embodiments and comparative examples of the present application can all be obtained commercially.
[0218] If no specific techniques or conditions are specified in the examples, the experiments were carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. All reagents or instruments used without specifying the manufacturer are commercially available conventional products.
[0219] 1. Preparation of Micro-mesoporous Materials
[0220] 1. COF-1 Synthesis
[0221] To the reactor, 0.1 g of hexa(4-formylphenyl)benzene and p-phenylenediamine in a molar ratio of approximately 1:1 was added, followed by 3 g of 1,4-dioxane and ultrasonication for 5 minutes. Under nitrogen, 0.3 g of a 6 mol / L acetic acid solution was slowly added, and the mixture was transferred to an oven at 120°C and reacted for 48 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor with acetone for 20 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, named COF-1. The reaction process of COF-1 is shown in Figure 1.
[0222] The adsorption capacity of COF-1 for nitrogen was measured using a Quantachrome (ASiQMVH002 5) gas adsorption instrument at standard atmospheric pressure (101 kPa). The gas used was 99.999% pure. The following testing steps were used: 100 mg of COF-1 was placed in a quartz sample tube and degassed at 120°C for 6 hours in a pre-treatment station on a rapid surface area analyzer. The gas adsorption experiment was performed on COF-1 using the gas adsorption instrument. Based on the nitrogen adsorption curves obtained, the pore size distribution (PSD) was calculated using nonlocal density functional theory (NLDFT). The pore size of the COF-1 internal pores was primarily concentrated around 0.67 nm, indicating that the pore size of the COF-1 internal pores is 0.67 nm.
[0223] 2. MOF-1 synthesis
[0224] Weigh 0.3787 g of N-methylimidazole and add 30 mL of ethanol to dissolve it (add a magnetic rod to the flask). Weigh 0.3798 g of zinc acetate and add 30 mL of ethanol to dissolve it. Then add this solution to the above solution, let it stand at 100°C for 12 h, and centrifuge to obtain a solid.
[0225] Using the same testing method as COF-1, the pore diameter of the internal pores of MOF-1 was measured to be 0.34 nm.
[0226] 3. COF-2 Synthesis
[0227] To a reactor, 0.1 g of 1,3,5-tris[4-amino(phenyl-4-yl)]benzene and 4,4′-(6-phenylphenanthrene-3,8-diacyl)benzaldehyde (at a molar ratio of approximately 1:1) were added, followed by 3 g of 1,4-dioxane, which was fully dissolved. Under nitrogen, 3 g of mesitylene (templating agent) was added. After 5 minutes of simmering, 0.3 g mol / L acetic acid solution was slowly added. The mixture was transferred to an oven and reacted at 120°C for 72 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor with methanol for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, named COF-2. The structural diagram of COF-2 is shown in Figure 2.
[0228] Using the same testing method as COF-1, the pore diameter of the internal pores of COF-2 was measured to be 4.8 nm.
[0229] 4. COF-3 Synthesis
[0230] To the reactor, 0.1 g of 1,3,5-triformaldehyde-2,4,6-methoxybenzene and p-1,3,5-triamino-2,4,6-methoxybenzene in a molar ratio of approximately 1:1 were added, followed by 3 g of 1,4-dioxane and 3 g of the template, mesitylene, and allowed to fully dissolve. Under nitrogen, 0.3 g of 6 mol / L acetic acid solution was slowly added. The mixture was transferred to an oven and reacted at 120°C for 72 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor using tetrahydrofuran for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, named COF-3. The structural diagram of COF-3 is shown in Figure 3.
[0231] Using the same testing method as COF-1, the pore diameter of the internal pores of COF-3 was measured to be 0.3 nm.
[0232] 5. COF-4 Synthesis
[0233] 0.1 g of 1,4-methylenediboronic acid-2,5-dimethylbenzene was added to the reactor, followed by 3 g of a 4:1 mixture of acetonitrile and 1,4-dioxane. After sonication, the mixture was thoroughly dissolved. The reactor was sealed with nitrogen and transferred to an oven at 90°C for 72 hours. The reaction mixture was filtered, and the residue was purified using a Soxhlet extractor with tetrahydrofuran for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, named COF-4. The structure of COF-4 is shown in Figure 4.
[0234] Using the same testing method as COF-1, the pore diameter of the internal pores of COF-4 was measured to be 0.8 nm.
[0235] 6. COF-5 Synthesis
[0236] To a reactor, 0.1 g of hydrazine hydrate and trialdehyde phloroglucinol in a molar ratio of approximately 1:1 was added, followed by 3 g of a 1:1 mixture of tetrahydrofuran and ethanol, allowing them to fully dissolve. Under nitrogen, 0.3 g of 6 mol / L acetic acid solution was slowly added. The mixture was transferred to an oven and reacted at 120°C for 120 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor using tetrahydrofuran for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, named COF-5. A schematic diagram of the COF-5 structure is shown in Figure 5.
[0237] Using the same testing method as COF-1, the pore diameter of the internal pores of COF-5 was measured to be 0.97 nm.
[0238] 7. COF-6 Synthesis
[0239] 0.1g of benzidine and trialdehyde phloroglucinol in a molar ratio of approximately 1:1 was added to a reactor, followed by 3g of a 1:1 mixture of tetrahydrofuran and ethanol, and allowed to dissolve thoroughly. Under nitrogen, 0.3g of 6mol / L acetic acid solution was slowly added. The mixture was transferred to an oven and reacted at 120°C for 120 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor using tetrahydrofuran for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, named COF-6. A schematic diagram of the COF-6 structure is shown in Figure 6.
[0240] Using the same testing method as COF-1, the pore diameter of the internal pores of COF-6 was measured to be 2 nm.
[0241] 8. COF-7 Synthesis
[0242] To a reactor, 0.1 g of 1,3,5-tris[4-amino(1,1-biphenyl-4-yl)]benzene and 4,4′-(6-phenylphenanthrene-3,8-diacyl)benzaldehyde (at a molar ratio of approximately 1:1) were added, followed by 3 g of 1,4-dioxane, which was fully dissolved. Under nitrogen, 3 g of mesitylene (a template) was added. After 5 minutes of simmering, 0.3 g mol / L acetic acid solution was slowly added. The mixture was transferred to an oven and reacted at 120°C for 72 hours. The reaction product was filtered, and the residue was purified in a Soxhlet extractor with methanol for 30 hours. The purified solid was then dried in a vacuum oven at 80°C for 24 hours to obtain the product, named COF-7. The structural diagram of COF-7 is shown in Figure 7.
[0243] Using the same testing method as COF-1, the pore diameter of the internal pores of COF-7 was measured to be 5.8 nm.
[0244] It should be noted that since COF materials synthesized using the same monomers have the same internal pore diameter, the resulting COF materials can further adjust the volume average particle size (Dv50) of the resulting COF material by controlling reaction conditions such as temperature and time during the COF material preparation process. For ease of description, COF materials synthesized using the same monomers and having the same internal pore diameter will be uniformly named in this application.
[0245] 2. Preparation of diaphragm
[0246] Example 1
[0247] Polyvinylidene fluoride (as a polymer) was dissolved in N-methylpyrrolidone until it was clear to prepare a polymer solution with a mass percentage concentration of 5%; then COF-1 (as a barrier material) was added and dispersed at a high speed of 1000 rpm for 12 hours to prepare a slurry.
[0248] A PE film with a thickness of 7 μm and a pore size of 20 nm (as a polymer layer) was spread flat in a Buchner funnel, the slurry was added, and the film was filtered for 2 h. Deionized water was then added to the Buchner funnel to wash away the residual slurry. The PE film was then removed from the Buchner funnel and dried in a vacuum drying oven at 80°C for 12 h to obtain a diaphragm.
[0249] Example 2-37
[0250] The preparation methods of the diaphragms in Examples 2-15, 18, and 22-34 are basically similar to the preparation method of the diaphragm in Example 1. The main differences are: one or more of the following: the type of barrier material, the volume average particle size Dv50 of the barrier material, the pore size of the pores inside the barrier material, the thickness of the barrier layer, the ratio of the thickness of the barrier layer to the volume average particle size Dv50 of the barrier material, the air permeability of the barrier layer, the conductivity of the ion-conducting inorganic material, the type and / or weight average molecular weight and / or swelling degree of the polymer, the mass proportion of the polymer layer in the barrier layer, and the area proportion of the barrier material in the barrier layer. See Table 1 for details.
[0251] The preparation methods of the diaphragms in Examples 16-17, Examples 19-21, and Examples 35-37 are different from the preparation method of the diaphragm in Example 1, and one or more of the following are used: the type of barrier material, the volume average particle size Dv50 of the barrier material, the pore size of the internal pores of the barrier material, the thickness of the barrier layer, the ratio of the barrier layer thickness to the volume average particle size Dv50 of the barrier material, the air permeability of the barrier layer, the conductivity of the ion-conducting inorganic material, the type and / or weight average molecular weight and / or swelling degree of the polymer, the mass proportion of the polymer layer in the barrier layer, the area proportion of the barrier material in the barrier layer, the type of polymer, the type of support layer, the pore size of the support layer, and the thickness of the diaphragm. For details, see Table 1. It should be noted that the thickness of the diaphragm in Examples 16-17, Examples 19-21, and Examples 36-37 refers to the thickness of the diaphragm when both the support layer and the barrier layer are included.
[0252] The separator in Example 16 was prepared by dissolving polyvinylidene fluoride (PVDF) in N-methylpyrrolidone until clear. LATP (LATP) was then added and dispersed at 2000 rpm for 12 hours to obtain a slurry. The slurry was then coated onto a 7-μm-thick PE film (supporting layer) to form a 2-μm-thick barrier layer. The blade used for the coating was 5 μm high and moved at a speed of 30 mm / s. The PE film loaded with the barrier layer was then dried in a vacuum drying oven at 80°C for 12 hours to obtain a primary barrier layer. The PE film loaded with the once-treated barrier layer was spread flat in a Buchner funnel, a polyvinylidene fluoride solution with a mass percentage concentration of 5% was added, and the film was filtered for 2 hours; then deionized water was added to the Buchner funnel to wash away the residual polyvinylidene fluoride solution; the PE film was removed from the Buchner funnel and dried in a vacuum drying oven at 80°C for 12 hours to obtain a diaphragm.
[0253] The separator in Example 17 was prepared by dissolving polyvinylidene fluoride (PVDF) as the polymer in N-methylpyrrolidone until clear. LLTO (barrier material) was then added and dispersed at 2000 rpm for 12 hours to obtain a slurry. The slurry was then coated onto a 7-μm-thick PE film (supporting layer) to form a barrier layer with a coating thickness of 2 μm. The blade used for the coating was 5 μm high and moved at a speed of 30 mm / s. The PE film loaded with the barrier layer was then dried in a vacuum drying oven at 80°C for 12 hours to obtain a primary barrier layer. The PE film loaded with the once-treated barrier layer was spread flat in a Buchner funnel, a polyvinylidene fluoride solution with a mass percentage concentration of 5% was added, and the film was filtered for 2 hours; then deionized water was added to the Buchner funnel to wash away the residual polyvinylidene fluoride solution; the PE film was removed from the Buchner funnel and dried in a vacuum drying oven at 80°C for 12 hours to obtain a diaphragm.
[0254] The preparation method of the diaphragm in Example 19 is as follows: polyimide (as a polymer) is dissolved in N-methylpyrrolidone until it is clear, and a polymer solution with a mass percentage concentration of 5% is prepared. The polymer solution is scraped onto a PE film (as a support layer) with a thickness of 7 μm, and the coating thickness is 1 μm to obtain a polymer layer supported on the PE film; wherein, the height of the scraper used for scraping is 10 μm, and the coating machine drives the scraper to move at a speed of 30 mm / s. Before the polymer layer is formed into a film, LSPS (as a barrier material) is evenly sprayed on the surface of the polymer layer, and the LSPS is embedded in the polymer layer by rolling, and then dried at 80°C in a vacuum drying oven for 12 hours to obtain a diaphragm.
[0255] The diaphragm in Example 20 was prepared by dissolving polyimide (as a polymer) in N-methylpyrrolidone until clear to prepare a polymer solution with a mass percent concentration of 5%. The polymer solution was then applied to a 7 μm thick PE film (as a support layer) with a coating thickness of 1 μm to obtain a polymer layer supported on the PE film. The blade used for the coating was 10 μm high and the coating machine moved the blade at a speed of 30 mm / s. Before the polymer layer formed, LATP (as a barrier material) was evenly sprayed onto the surface of the polymer layer. The LATP was embedded in the polymer layer by roller pressing, and then dried in a vacuum drying oven at 80°C for 12 hours to obtain the diaphragm.
[0256] The preparation method of the diaphragm in Example 21 is as follows: polyvinylidene fluoride (as a polymer) is dissolved in N-methylpyrrolidone until it is clear to prepare a polymer solution with a mass percentage concentration of 5%. The polymer solution is coated on a 7μm thick PE film (as a support layer) with a coating thickness of 1μm to obtain a polymer layer supported on the PE film; wherein, the height of the scraper used during the scraping is 10μm, and the coating machine drives the scraper at a speed of 30mm / s. Before the polymer layer is formed into a film, LATP (as a barrier material) is evenly sprayed on the surface of the polymer layer, and the LATP is embedded in the polymer layer by rolling. Then, it is dried at 80°C in a vacuum drying oven for 12h to obtain a diaphragm.
[0257] The preparation method of the diaphragm in Example 35 is as follows: polyvinylidene fluoride (as a polymer) is dissolved in N-methylpyrrolidone until it is clear, and a polymer solution with a mass percentage concentration of 5% is prepared. The polymer solution is scraped onto a glass plate with a coating thickness of 5 μm to obtain a polymer layer loaded on the glass plate; wherein, the height of the scraper used for scraping is 10 μm, and the coating machine drives the scraper to move at a speed of 30 mm / s. Before the polymer layer is formed into a film, COF-1 (as a barrier material) is evenly sprayed on the surface of the polymer layer, and the COF-1 material is embedded in the polymer layer by rolling, and then dried at 80°C in a vacuum drying oven for 12 hours, and the glass plate is removed to obtain a diaphragm.
[0258] The preparation method of the diaphragm in Example 36 is as follows: polyvinylidene fluoride (as a polymer) is dissolved in N-methylpyrrolidone until it is clear, and a polymer solution with a mass percentage concentration of 5% is prepared. The polymer solution is scraped onto a PE film (as a support layer) with a thickness of 7 μm, and the coating thickness is 1 μm to obtain a polymer layer supported on the PE film; wherein, the height of the scraper used during scraping is 10 μm, and the coating machine drives the scraper to move at a speed of 30 mm / s. Before the polymer layer is formed into a film, COF-1 (as a barrier material) is evenly sprayed on the surface of the polymer layer, and the COF-1 material is embedded in the polymer layer by rolling, and then dried at 80°C in a vacuum drying oven for 12 hours to obtain a diaphragm.
[0259] The separator in Example 37 was prepared by dissolving polyvinylidene fluoride (PVDF) as the polymer in N-methylpyrrolidone until clear. COF-1 (COF-1) as the barrier material was then added and dispersed at 2000 rpm for 12 hours to obtain a slurry. The slurry was then coated onto a 7-μm-thick PP film (as the support layer) to form a barrier layer with a coating thickness of 2 μm. The blade used for the coating was 5 μm high and moved at a speed of 30 mm / s. The PP film loaded with the barrier layer was then dried in a vacuum drying oven at 80°C for 12 hours to obtain a primary barrier layer. The PP film loaded with a once-treated barrier layer was spread flat in a Buchner funnel, a polyvinylidene fluoride solution with a mass percentage concentration of 5% was added, and the film was filtered for 2 hours; then deionized water was added to the Buchner funnel to wash away the residual polyvinylidene fluoride solution; the PP film was removed from the Buchner funnel and dried in a vacuum drying oven at 80°C for 12 hours to obtain a diaphragm.
[0260] Comparative Example 1
[0261] In Comparative Example 1, an ordinary PP film was used as the separator.
[0262] Comparative Example 2
[0263] The preparation method of the diaphragm in Comparative Example 2 is basically similar to the preparation method of the diaphragm in Example 1, with the main difference being that only 1 / 2 of the area of the PE membrane is filtered during filtration, and the remaining portion is not processed. Detailed parameter settings are shown in Table 1.
[0264] Comparative Example 3
[0265] The preparation method of the separator in Comparative Example 3 is basically similar to that in Example 1, and the main differences are as follows: one or more of the type of the barrier material, the volume average particle size Dv50 of the barrier material, the pore diameter of the pores inside the barrier material, the thickness of the barrier layer, the ratio of the thickness of the barrier layer to the volume average particle size Dv50 of the barrier material, the air permeability of the barrier layer, the conductivity of the ion-conducting inorganic material, the type and / or weight average molecular weight and / or swelling degree of the polymer, the mass percentage of the polymer layer in the barrier layer, and the area percentage of the barrier material in the barrier layer are different. For details, see Table 1.
[0266]
[0267] It should be noted that the volume average particle size Dv50 of the above-mentioned barrier material is measured by laser particle size analysis using the Microtrac MRB S3500 series (Microtrac MRB S3500). The specific process is as follows: Take 2 g of the barrier material, add 20 mL of deionized water, and ultrasonicate for 5 min to ensure that the sample is completely dispersed to obtain a dispersion. Then, place the dispersion in the sample cell and test to obtain the volume average particle size Dv50 of the barrier material.
[0268] The pore diameter of the pores inside the above-mentioned barrier material COF-1 is obtained by the following method: Take the COF-1 material to be tested, use a gas sorption instrument of the model Quantachrome (ASiQMVH002 5) to measure the adsorption amount of N2 by the COF material under standard atmospheric pressure (101 kPa), and the purity of the gas used for the test is 99.999%. Add 100 mg of the COF material to a quartz sample tube and degas it under vacuum at 120 °C for 6 h on the pretreatment station of a rapid specific surface area analyzer. Conduct a gas adsorption experiment on the COF material using a gas sorption instrument. According to the obtained nitrogen adsorption curve, use the non-local density functional theory model (NLDFT) to calculate the BET specific surface area of the COF material for the adsorption data in the low-pressure range (0.0255 < P / P0 < 0.2), and calculate the pore volume at P / P0 = 0.99. The pore size distribution (PSD) is obtained by calculation using the non-local density functional theory (NLDFT).
[0269] The pore size of the internal pores of the above-mentioned barrier material MOF-1 was measured by the following method: Take the MOF-1 material to be measured, use a gas sorption analyzer of model Quantachrome (ASiQMVH002 5) to measure the adsorption amount of N2 by the MOF material under standard atmospheric pressure (101 kPa), and the purity of the gas used for the measurement is 99.999%; Add 100 mg of the MOF material into a quartz sample tube, and perform vacuum degassing at 120 °C for 6 h on the pretreatment station of a rapid specific surface area analyzer. Use the gas sorption analyzer to conduct a gas adsorption experiment on the MOF material. According to the obtained nitrogen adsorption curve, use the nonlocal density functional theory model (NLDFT) to calculate the BET specific surface area of the MOF material for the adsorption data in the low-pressure range (0.0255 < P / P0 < 0.2), and calculate the pore volume at P / P0 = 0.99; The pore size distribution (PSD) is obtained by calculating with the nonlocal density functional theory (NLDFT).
[0270] The electrical conductivities of the above-mentioned barrier materials LLZO, LLTO, LATP, LAGP and LSPS were measured by the following method: Fabricate the ionic-conducting inorganic material into a solid electrolyte ceramic sample, perform an alternating current impedance test on the solid electrolyte ceramic sample through a CHI660E electrochemical workstation, clamp the sample with conductive silver paste as the electrode (i.e., silver plating on both sides of the electrolyte wafer), and the test frequency range is 10^6 Hz - 0.1 Hz. After obtaining the total impedance value by analyzing the impedance spectrum obtained through the test, calculate the corresponding total ionic conductivity. The ionic conductivity is calculated according to the formula σ = d / (R×P)×1000. Where σ is the ionic conductivity, with the unit of mS·cm -1 , d is the thickness of the electrolyte wafer, with the unit of cm; R is the impedance value of the electrolyte wafer measured by the electrochemical workstation, with the unit of ohm; P is the size of the bottom area of the electrolyte wafer, with the unit of cm 2 .
[0271] The area ratio of the above-mentioned barrier material in the barrier layer was measured by the following method: Take the SEM image of the barrier layer by using a scanning electron microscope, calculate the total area of the barrier material and the area of the barrier layer based on the SEM image of the barrier layer; According to the formula: total area of the barrier material / area of the barrier layer, calculate the area ratio of the barrier material in the barrier layer.
[0272] The swelling degree of the above-mentioned polymer was measured by the following method: At 25 °C, scrape the polymer sample on a glass plate to form a film. Take a polymer film piece with a size of 1 cm × 1 cm, after vacuum drying at 60 °C, weigh it with a balance as M1. Immerse the polymer film piece in dimethyl carbonate for 12 h, take it out and wipe off the surface solution with dust-free paper, and weigh it as M2; Then calculate the swelling degree of the polymer according to the formula C = (M2 - M1) / M1×100%.
[0273] The mass proportion of the above-mentioned polymer layer in the barrier layer is tested using the following method: The barrier layer components are analyzed using a thermogravimetric-differential scanning calorimeter: 15-25 mg of the barrier layer is placed in an alumina crucible with nitrogen as the protective gas. After preheating at 25°C for 30 minutes, the temperature is raised to 600°C at a rate of 2°C / 10 minutes. The content of each component is determined based on the weight change and heat change.
[0274] The air permeability test method for the aforementioned barrier layer is as follows: The barrier layer is flattened in a flat, oil-free location, placed on the outlet of an air compressor cylinder, and screwed securely. Once the barrier layer is secured, the air within is compressed using the cylinder's own weight, floating on the liquid. As the air passes through the sample, the cylinder falls steadily. The time required for a certain volume of air to pass through the sample is measured, and the air permeability is calculated based on this time. The air column volume is 100cc, and the test area is 6.45cm. 2 ; Sample area > 6cm×6cm.
[0275] The average pore size of the support layer pores mentioned above was tested using the following method: the pore size of the diaphragm was tested using the PMI multifunctional pore size analyzer from PMI, USA. The sample to be tested was cut into discs with a diameter of 0.5 cm, soaked in the infiltration liquid for 10 minutes, and transferred to the fixture with tweezers. The pressure range was set to 0-500PSI for pore size testing.
[0276] The thickness of the above-mentioned diaphragm is measured by the following method: calibrate the micrometer, then place the diaphragm between the two anvils, gently rotate the sleeve until a sound is heard, and read the thickness of the diaphragm.
[0277] When the diaphragm does not contain a support layer, the thickness of the barrier layer mentioned above is measured by the following method: calibrate the micrometer, then place the diaphragm between the two anvils, gently rotate the sleeve until it makes a sound, and read the thickness of the diaphragm.
[0278] When the diaphragm contains both a support layer and a barrier layer, the thickness of the barrier layer mentioned above is measured using the following method: first, calibrate the micrometer, then place the diaphragm between the two anvils, gently rotate the sleeve until a sound is heard, and read the reading to record the diaphragm thickness; remove the diaphragm, remove the barrier layer to obtain the support layer, repeat the above measurement process to measure the thickness of the support layer; subtract the thickness of the support layer from the thickness of the diaphragm to obtain the thickness of the barrier layer.
[0279] The weight average molecular weight of the above-mentioned polymers was measured by gel permeation chromatography (GPC).
[0280] 3. Diaphragm performance measurement
[0281] 1. Diaphragm air permeability
[0282] Flatten the diaphragm, select a flat, oil-free location, place it on the outlet of the air compressor, and tighten it securely. Once the diaphragm is secured, use the weight of the cylinder floating on the liquid to compress the air inside. As the air passes through the sample, the cylinder will fall steadily. Measure the time it takes for a certain volume of air to pass through the sample, and use this time to calculate the air permeability. The air column volume is 100cc, and the test area is 6.45cm. 2 ; Sample area > 6 cm × 6 cm. Detailed results are shown in Table 2.
[0283] 4. Preparation of Secondary Batteries
[0284] 1. Preparation of positive electrode sheet
[0285] LNMO(LiNi 0.5 Mn 1.5 O4 (as the positive electrode active material), conductive carbon black (as the conductive agent) and polyvinylidene fluoride (as the binder) are mixed in a mass ratio of 96:2.5:1.5, and then N-methylpyrrolidone is added and stirred to disperse into a positive electrode slurry. The positive electrode slurry is coated on both sides of the aluminum foil, dried, cold pressed, and cut to produce a positive electrode sheet. The positive electrode powder is coated on one side with a unit area density of 0.02g / cm 2 .
[0286] 2. Preparation of negative electrode sheet
[0287] Artificial graphite (as negative electrode active material), conductive carbon black (as conductive agent), styrene-butadiene rubber (as binder) and sodium carboxymethyl cellulose (as thickener) are mixed in a mass ratio of 96:1:1:2, and then deionized water is added and stirred to disperse into a negative electrode slurry. The negative electrode slurry is evenly coated on one side of the copper foil, dried, cold pressed, and cut to produce a negative electrode sheet. The negative electrode powder is coated on one side with a unit area density of 0.008 g / cm 2 .
[0288] 3. Preparation of Electrolyte
[0289] Preparation of positive electrode electrolyte: In an argon-filled glove box (moisture <10ppm, oxygen <10ppm), 1wt% of vinylidene sulfate and 1wt% of propane sultone were added to methyl trifluoroethyl carbonate (FEMC) and mixed thoroughly. Finally, lithium hexafluorophosphate (LiPF6) was added to the mixed solution until the molar concentration of LiPF6 was 1mol / L to prepare the positive electrode electrolyte.
[0290] Preparation of negative electrode electrolyte: In an argon-filled glove box (moisture <10ppm, oxygen <10ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were uniformly mixed in a mass ratio of EC:EMC=7:3, 1wt% of vinylene carbonate and 1wt% of fluoroethylene carbonate (FEC) were added to the mixture and mixed thoroughly, and finally lithium hexafluorophosphate (LiPF6) was slowly added to the mixed solution until the molar concentration of LiPF6 was 1mol / L to prepare the negative electrode electrolyte.
[0291] 4. The isolation membranes in the above embodiments and comparative examples were used.
[0292] 5. Preparation of battery cells
[0293] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play a role of isolation. The three are placed in an aluminum-plastic bag with the same length and width as the separator. The other three sides of the aluminum-plastic bag except the opening are heat-sealed together with the separator. The separator and the aluminum-plastic bag form a dense positive electrode chamber and a negative electrode chamber. The positive electrode chamber side is injected with positive electrode electrolyte, and the negative electrode chamber side is injected with negative electrode electrolyte. The battery cells are sealed to obtain a battery cell, and then the battery cell is placed in a battery case, formed, and allowed to stand to obtain a secondary battery.
[0294] 5. Secondary battery performance test
[0295] 1. Cyclic performance test
[0296] At 25°C, the secondary batteries in each of the examples and comparative examples were charged at a constant current of 0.1C to 4.9V, then charged at a constant voltage of 4.9V to a current of 0.05C. After standing for 5 minutes, the secondary batteries were discharged at a constant current of 0.1C to 3.5V. This constitutes one charge-discharge cycle, and the discharge capacity at this point is the initial discharge capacity of the secondary battery. The secondary batteries were cycled in this manner until the discharge capacity after the cycle decayed to 80% of the initial discharge capacity. The test was terminated, and the number of cycles completed was recorded.
[0297] 2. Storage performance test
[0298] At 25°C, the secondary batteries in each of the above examples and comparative examples were charged at a constant current of 0.1C to 4.9V, then charged at a constant voltage of 4.9V to a current of 0.05C, at which point the secondary batteries were fully charged. The fully charged secondary batteries were stored at 25°C, removed every five days, and discharged at a constant current of 0.1C to 3.5V. The discharge capacity after storage was measured. The secondary batteries were then fully charged as described above and stored again at 25°C until the discharge capacity after storage decayed to 70% of the initial discharge capacity. The test was then terminated, and the total number of days the secondary batteries were stored was recorded.
[0299] 3. Impedance test
[0300] Extract the voltage V1 during the first cycle capacity test in "1. Cycling Performance Test" after charging and standing for 5 minutes, and extract the voltage V2 after 0.1C discharge for 30 seconds. The initial impedance of the cycle is (V1-V2) / (0.1C).
[0301] The performance test results of the above embodiments and comparative examples are shown in Table 2.
[0302] Table 2
[0303] As shown in the results of Examples 1-37 in Table 2, by regulating the volume average particle size Dv50 of the barrier material and the thickness of the barrier layer, the air permeability of the barrier layer is ≥300s / 100mL. The barrier layer can significantly inhibit the penetration of solvents, additives, and by-products in the electrolyte, thereby eliminating the battery capacity decay caused by the interaction between the positive and negative electrodes.
[0304] The main difference between Examples 1-6 lies in the ratio of the barrier layer thickness to the volume average particle size Dv50 of the barrier material, with Example 6 having the highest ratio. Compared with Examples 1-5, Example 6 exhibits significantly lower cycles and storage days, while significantly higher cycle impedance. This is presumably because a high d1 / D ratio can lead to overly dense packing of barrier material particles, resulting in excessive contact surface area between the particles and potentially slowing lithium ion transport through the barrier material.
[0305] The difference between Example 3 and Examples 7-12 lies in the pore diameter of the barrier material. The pore diameter of the barrier material in Example 12 is the largest. Compared with Example 3 and Examples 7-11, the number of cycles and storage days in Example 12 are significantly reduced. This is presumably because when the pore diameter of the barrier material is too large, the barrier effect of the separator is weakened, potentially allowing some substances in the electrolyte other than lithium ions to pass through the separator.
[0306] Compared with Example 14, Examples 16-17, and Examples 19-21, the cycle impedance of the secondary battery in Example 15 is significantly increased; it is speculated that this may be due to the poor conductivity of LLZO, which leads to the increase in the impedance of the secondary battery.
[0307] Compared with Example 14, Examples 16-17 and Examples 19-21, the cycle impedance of the secondary battery in Example 18 is significantly increased; it is speculated that this may be due to the excessively large ratio of the barrier layer thickness to the volume average particle size Dv50 of the barrier material, which leads to a significant increase in the impedance of the secondary battery.
[0308] The difference between Example 3 and Examples 24-30 lies in the different area ratios of the barrier material in the barrier layer and the mass ratio of the polymer layer in the barrier layer. Example 28 has the smallest area ratio of the barrier material in the barrier layer. Compared with Example 3, Examples 24-27, and Examples 29-30, the secondary battery in Example 28 exhibits a significant decrease in cycle times and a significant increase in impedance. This is presumably because a low area ratio of the barrier material in the barrier layer can reduce lithium ion transport channels, worsen battery impedance, and reduce both cycling and storage performance.
[0309] The difference between Example 3 and Examples 31-34 lies in the different weight-average molecular weights of the polymers. The weight-average molecular weight of the polymer in Example 31 is the smallest. Compared with Example 3 and Examples 32-34, the number of cycles and storage days in Example 31 are significantly reduced. It is speculated that when the weight-average molecular weight of the polymer is too low, the barrier layer formed has poor density, which may weaken the barrier effect of the barrier layer, allowing some substances in the electrolyte other than lithium ions to penetrate the separator.
[0310] The results of Examples 1-37 and Comparative Example 1 demonstrate that the membranes of the present application exhibit significantly lower air permeability compared to conventional membranes, and that secondary batteries formed using the membranes of the present application exhibit significantly increased cycle times and storage life. This demonstrates that the membranes of the present application significantly inhibit the passage of solvents, additives, and byproducts in the electrolyte through the barrier layer, eliminating battery capacity degradation caused by interaction between the positive and negative electrodes and improving cycling and storage performance.
[0311] It can be seen from the results of Example 1 and Comparative Example 2 that when the air permeability of the barrier layer is lower than 300 s / 100 mL, the barrier layer may weaken the inhibitory effect on the interaction between the positive electrode and the negative electrode.
[0312] The above description is merely a specific embodiment of the present application, but the scope of protection of the present application is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present application, and such modifications or substitutions should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.
Claims
1. A membrane comprising a barrier layer, the barrier layer comprising a polymer layer and a barrier material at least partially embedded in the polymer layer; in, The barrier material includes one or more of a micro-mesoporous material and an ion-conducting inorganic material; the volume average particle size Dv50 of the barrier material is denoted as D, the thickness of the barrier layer is denoted as d1, and the volume average particle size Dv50 of the barrier material and the thickness of the barrier layer satisfy: 0.2≤d1 / D≤1000; The air permeability of the barrier layer is ≥300s / 100mL.
2. The diaphragm according to claim 1, wherein the air permeability of the barrier layer is ≥500s / 100mL; optionally, the air permeability of the barrier layer is ≥800s / 100mL.
3. The diaphragm according to any one of claims 1 to 2, wherein the volume average particle size Dv50 of the barrier material and the thickness of the barrier layer satisfy: 1≤d1 / D≤500; optionally 1≤d1 / D≤300.
4. The diaphragm according to any one of claims 1 to 3, wherein the volume average particle size Dv50 of the barrier material satisfies: 0.005 μm ≤ D ≤ 10 μm; optionally 0.007 μm ≤ D ≤ 5 μm; further optionally 0.01 μm ≤ D ≤ 1 μm. 5 . The diaphragm according to claim 1 , wherein the thickness of the barrier layer satisfies: 0.007 μm≤d1≤50 μm; optionally 0.2 μm≤d1≤15 μm.
6. The membrane according to any one of claims 1 to 5, wherein the micro-mesoporous material comprises one or more of a covalent organic framework material and a metal organic framework material; Optionally, the connecting groups between the monomers polymerized to form the covalent organic framework material include One or more of a boryloxy group, -C=N-, a triazine group, -C=NN=C-, -C=C-, -CO-NH-, -C=N-NH-CO- and an imidazole group.
7. The diaphragm according to any one of claims 1 to 6, wherein the ion-conducting inorganic material comprises LLZO, LLTO, LATP, LAGP, LSPS, and one or more of coatings, dopants and / or dopants with coating layers of the above substances.
8. The diaphragm according to any one of claims 6 to 7, wherein the pore size of the internal pores of the micro-mesoporous material is denoted as d2, and the pore size of the internal pores of the micro-mesoporous material satisfies: 0.04nm≤d2≤5nm; optionally 0.3nm≤d2≤2nm.
9. The membrane according to any one of claims 6 to 8, wherein the conductivity of the ion-conducting inorganic material is ≥ 0.0001 mS·cm at 25°C -1 ; Optionally, the electrical conductivity of the ion-conducting inorganic material is ≥ 0.001 mS·cm at 25°C. -1 ; Further optionally, the conductivity of the ion-conducting inorganic material is ≥ 0.01 mS·cm at 25°C -1 .
10. The diaphragm according to any one of claims 1 to 9, wherein the area proportion of the barrier material in the barrier layer is 30%-99%; optionally 50%-99%; further optionally 70%-99%.
11. The separator according to any one of claims 1 to 10, wherein the polymer layer has at least one of the following features (1) to (3): (1) The polymer layer comprises a polymer having a swelling degree ≤ 10%; Optionally, the polymer includes one or more of polyethylene, polypropylene, polyimide and polyvinylidene fluoride; (2) The mass proportion of the polymer layer in the barrier layer is ≤50%; Optionally, the mass of the polymer layer in the barrier layer is 2%-30%; further optionally, 5%-15%; (3) The polymer layer comprises a polymer having a weight average molecular weight of 1W-200W; Optionally, the polymer layer comprises a polymer having a weight average molecular weight of 2W-150W; Further optionally, the polymer layer includes a polymer with a weight average molecular weight of 10W-100W. 12 . The diaphragm according to claim 1 , wherein the diaphragm further comprises a support layer, and the barrier layer is located on at least one side of the support layer.
13. The diaphragm according to claim 12, wherein the support layer has at least one of the following features (1)-(3): (1) The support layer has pores, and the average pore size of the pores of the support layer is 20nm-1000nm; optionally 100nm-500nm; (2) The material of the support layer includes one or more of polyethylene, polypropylene, polyimide and polyvinylidene fluoride. 14 . The diaphragm according to claim 12 , wherein the thickness of the diaphragm is 2 μm-12 μm; optionally 3 μm-10 μm; further optionally 5 μm-7 μm.
15. The diaphragm according to any one of claims 1 to 14, wherein the diaphragm has at least one of the following features: (1) The air permeability of the diaphragm is ≥300s / 100mL; optionally, the air permeability of the diaphragm is ≥500s / 100mL; further optionally, the air permeability of the diaphragm is ≥800s / 100mL; (2) The tensile strength of the diaphragm is ≥1000 MPa; optionally, the tensile strength of the diaphragm is ≥1200 MPa; further optionally, the tensile strength of the diaphragm is ≥1500 MPa.
16. A secondary battery comprising a positive electrode sheet, a negative electrode sheet, a positive electrode electrolyte, a negative electrode electrolyte and a separator as claimed in any one of claims 1 to 15; The separator is located between the positive electrode sheet and the negative electrode sheet, and the positive electrode electrolyte is located between the positive electrode sheet and the separator. The negative electrode electrolyte is located between the negative electrode plate and the isolation membrane; one or more of the solvent, lithium salt and additive contained in the positive electrode electrolyte and the negative electrode electrolyte are different.
17. The secondary battery according to claim 16, wherein the solvent of the positive electrode electrolyte is different from the solvent of the negative electrode electrolyte; Optionally, the solvent of the positive electrode electrolyte includes one or more of carbonate solvents, fluorocarbonate solvents, fluorocarboxylate solvents, sulfone solvents, fluorosulfone solvents, phosphate solvents, borate solvents and nitrile solvents; Optionally, the solvent of the negative electrode electrolyte includes one or more of carbonate solvents, carboxylate solvents, ether solvents, fluorinated carboxylate solvents and fluorinated carbonate solvents.
18. The secondary battery according to claim 17, wherein the fluorocarbonate solvent comprises one or more of methyl trifluoroethyl carbonate, bis(trifluoromethyl) carbonate, bis(trifluoroethyl) carbonate, 4-trifluoromethyl ethylene carbonate, bisfluoroethylene carbonate, trifluoromethyl trifluoroethyl carbonate, trifluoropropyl carbonate and 2,2-difluoroethyl methyl carbonate; The fluorocarboxylic acid ester solvent includes one or more of trifluoroethyl 3,3,3-trifluoroacetate, 2,2-difluoroethyl acetate, ethyl difluoroacetate and 2,2,2-trifluoroethyl acetate; The sulfone solvent includes one or more of sulfolane, dimethyl sulfone, diethyl sulfone, methyl ethyl sulfone, methyl isopropyl sulfone, dimethyl sulfoxide, diethyl sulfoxide and methyl ethyl sulfoxide; The fluorinated sulfone solvent includes one or more of methyl trifluoromethyl sulfone, ethyl trifluoromethyl sulfone, propyl trifluoromethyl sulfone, methyl trifluoroethyl sulfone, methyl trifluoropropyl sulfone, 1,1,2,2-tetrafluoropropyl methyl sulfone, trifluoromethyl isopropyl sulfone and methyl hexafluoroisopropyl sulfone; The phosphate ester solvent includes one or more of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, isopropyl phosphate, tris(hexafluoroisopropyl) phosphate and tris(2,2,2-trifluoroethyl) phosphate; The borate ester solvent includes one or more of trimethyl borate, triethyl borate, tri(hexafluoroisopropyl) borate and tri(2,2,2-trifluoroethyl) borate; The nitrile solvent includes one or more of acetonitrile, succinonitrile, succinonitrile, glutaronitrile, adiponitrile, 1,4-dicyano-2-butene, 1,3,6-hexanetrinitrile, ethylene glycol dipropionitrile ether and 1,2,3-tricyanoethoxy; The carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and ethylene carbonate; The carboxylate solvent includes one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate and propyl propionate; The ether solvent includes one or more of 1,2-dimethoxyethane, tetraethanol dimethyl ether, γ-butyrolactone and tetrahydrofuran.
19. The secondary battery according to any one of claims 16 to 18, wherein the lithium salt of the positive electrode electrolyte is different from the lithium salt of the negative electrode electrolyte; Optionally, the lithium salt of the positive electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(oxalatoborate); Optionally, the lithium salt of the negative electrode electrolyte includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide and lithium bis(oxalatoborate).
20. An electrical device comprising the secondary battery according to any one of claims 16 to 19.